Integrative transcriptomic profiling identifies LINC02365-associated regulatory networks in hepatocellular carcinoma - Peter Kisembo; Christian Cedric Bongolo; Mengqi Wei; Feng Lian Liu; Chang Wu; Shanshan Gao; Fang Zheng; Simon Peter Rugera; Jian Cheng Tu (Functional & Integrative Genomics, 2026)

Dynamic response of offshore wind turbine supported by suction bucket in sands under multi-hazard loads considering the scour-hole dimensions - Xinglei Cheng; Zheng Chong; Jingyu Liang; Xuyue Wang; Wenbo Tu; Zhongxian Liu (Soil Dynamics and Earthquake Engineering, 2026)

Mn spin-state modulation at directional C-N-Mn electron bridge enables selective and sustained PMS activation for deep contaminant mineralization - Rentao Zhou; Junjie Cheng; Xinman Tu; Xinding Lv; Pengxuan Wu; Li Zhang; Xinjie Yang; Honghu Zeng; Jianping Zou (Journal of Environmental Chemical Engineering, 2026)

Rearranged phenylpropanoyl-phloroglucinol dimers from the flowers of Xanthostemon chrysanthus - Qiong Zhan; Fen Liu; Yu-Xin He; Le-Yi Chen; Zhen Wang; Zheng-Chao Tu; Jun Xu; Min-Jing Cheng; Wen-Jing Wang; Wen-Cai Ye; Lei Wang (Phytochemistry, 2026)

Global Freshwater Resistomes Reveal Environmental Signatures Associated with the Burden of Drug-resistant Tuberculosis - Tong Li; Jiahui Lv; Yunye Tu; Li Cheng; Hongjun Xiao; Yanping Sun; Jia-xin Li; Mingkun Lv; Jingkai Yang; Guanghui Wang; Zexi Tang; Yajie Liu; et al. (Environmental Pollution, 2026)

Response of pressurized municipal pipelines to tunneling - Ping Wu; Cheng Kang; Rongzhu Liang; Wenbing Wu; Lv Liu; Shifang Tu; Changjiang Guo (Transportation Geotechnics, 2026)

Significant crust-thinning beneath the Ilan Plain of Taiwan for revealing westward impingement of the Okinawa Trough opening into Taiwan Orogeny - Ya-Chuan Lai; Cheng-Horng Lin; Min-Hung Shih; Yoko Tao-Lin Tu; Hsin-Chieh Pu; Wen-Yen Chang (Tectonophysics, 2026)

Uncovering an aseismic slab for showing the flipping of subduction polarity in the Taiwan area - Lin Cheng-Horng; Min-Hung Shih; Ya-Chuan Lai; Yoko Tao-Lin Tu; Hsin-Chieh Pu; Wen-Yen Chang (Journal of Asian Earth Sciences, 2026)

Interactions between medicinal plants and rhizospheric microbial secondary metabolites: Mechanisms, effects, and biotechnological applications - Karlia Meitha; Chen-Hui Kuo; Tu-Trinh Thi Truong; Chieh Chang; Tsai-Wen Hsu; Miaw-Ling Chen; Chao-Li Huang; Takashi Gojobori; Cheng-Han Yang (Ecological Genetics and Genomics, 2026)

Engineering of glycerol-derived aldolase pathway improves D-allulose synthesis in a glucose–glycerol dual-carbon system - Yifan Tu; Jing Lv; Mulan Wang; Tanxiang Huang; Lei Hu; Chen Liang; Xiyao Cheng; Jidong Liu (Archives of Microbiology, 2026)

A tetrahedral framework nucleic acid-based co-delivery platform enhances the antibacterial activity of nisin and quercetin against MRSA - Jiuyan Zhang; Ruiyuan Shi; Jiajian Liang; Yingqing Liu; Zhao Tu; Xiaonan Wang; Likai Hu; Chengbao Huang; Lingyan Cheng; Jie Wang; Xiang Fang; Li Wang (Critical Reviews in Food Science and Nutrition, 2026)

Influence of atomization characteristics of hydrophilic SiO2 nanofluid on fine coal dust suppression performance - Fanbo Jin; Shihang Li; Kunkun Tu; Shuda Hu; Zijie Li; Hui Cheng; Haonan Luo; Daolong Yang (Fuel, 2026)

Mechanisms of action of natural plant-derived bioactive compounds in treating intestinal tight junctions dysfunction - Jiduo Han; Ziliang Xiao; Lingyu Yang; Jianfang Feng; Yi Jin; Meng Cheng; Liangxing Tu (Phytochemistry Reviews, 2026)

Single-BDS GNSS-R water surface altimetry and performance analysis - Peiyuan Wang; Junqiang Han; Fang Cheng; Pengfei Zhang; Xiaolei Wang; Rui Tu; Weisheng Wang; Majid Gulayozov; Yaoming Li; Xiaochun Lu (Earth Science Informatics, 2026)

Design, synthesis, and anti-prostate cancer activity evaluation of novel thieno[2,3-b]pyridine derivatives as potential BLM helicase inhibitors - Wei Tu; Ningning Zan; Xinyu Liu; Gang Yu; Xiaoping Zeng; Yafang Zhou; Jia Yu; Xueling Meng; Kun Liu; Xiaolin Peng; Sha Cheng; Bixue Xu; et al. (Molecular Diversity, 2026)

S6 and S8 as the dominant neutralizing epitopes of tilapia lake virus and their potential use as vaccines - Jie Leng; Jie Yu; Hui-Hui Hu; Yun-Yao Tu; Cheng-Ke Zhu; Qun Lu; Tao He; Ming-Ji Lv; Song Zhu (Aquaculture, 2026)

Uncovering emerging organophosphate esters in chemical parks using nontarget screening method: Near-field concentration changes and ToxPi priorities - Weikun Meng; Cheng Yang; Yuanyang Tu; Bingqing Zhu; Yue Pan; Langjie Ye; Wenjing Sun; Shui Wang; Guanyong Su; Wei Liu (Environmental Research, 2026)

Engineering a 2-methylimidazole framework nanozyme for efficient oxidation of lactose to lactobionic acid under mild conditions - Donghui Xie; Yanna Jiao; Shaoyi Yu; Jia Tu; Yunhui Cheng; Xiaohong He; Daichen Mu; Keyu Xing; Zhou Xu (Journal of Environmental Chemical Engineering, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Integrative miRNA-mRNA-lncRNA Analysis Unveils Regulatory Networks Involved Clonal Reproduction of Root Sprouting in Toona fargesii - Jiaming Tie; Qiangqiang Li; Qiangqiang Cheng; Qiuwei Zhong; Zhonghua Tu; Rongxi Sun; Yao Xiao; Chunce Guo; Lu Zhang; Jikai Ma (Plant Molecular Biology Reporter, 2026)

Drying-wetting cycles alter the balance between physical fragmentation and leaching during leaf litter decomposition: a laboratory incubation experiment - Le-Lin Yu; Rui-Jing Chai; Qi-Han Tu; An He; Le-Cheng Ai; Rong Mao (Plant and Soil, 2026)

The neuroprotective effect of Cucurbitacin B against Aβ and tau toxicities requires functional HDAC6 and stress granule pathways - Xiaohui Tu; Minglv Fang; Yingxuan Yan; Ying Liu; Jing Yu; Liang Chen; Lu Zhang; Cheng Huang; Shengjie Fan (Biogerontology, 2026)

LEO-based interpolation methods comparison for regional augmented PPP - Jing Fang; Rui Tu; Runzhi Zhang; Fang Cheng; Xiaochun Lu (Acta Geodaetica et Geophysica, 2026)

Shorter to be effective: subanesthetic-dose ketamine infusion reduces the global and regional path length of brain functional connectivity in patients with treatment-resistant depression and suicidal ideation - Wei-Chen Lin; Li-Kai Cheng; Tung-Ping Su; Li-Fen Chen; Pei-Chi Tu; Cheng-Ta Li; Ya-Mei Bai; Shih-Jen Tsai; Mu-Hong Chen (Psychopharmacology, 2026)

Utilization of enzymes for improving fried flour products: Recent advances, applications, and regulations - Zihao Tu; David Julian McClements; Guifang Huang; Hao Cheng; Zhengyu Jin; Long Chen (Food Chemistry, 2026)

From haploid inducer to CMS donor: repurposing of CENH3 to create a CMS line in a single step in Brassica napus - Mengyu Lei; Muhammad Zeeshan Mola Bakhsh; Xiaoyu Zhang; Dongli He; Cheng Dai; Chaozhi Ma; Jingxin Tu; Jinxiong Shen; Jing Wen; Tingdong Fu; Bin Yi (Plant Cell Reports, 2026)

On-site, intelligent, and integrated monitoring of cereal safety: A review of advances in pathogens and toxins detection (2015-2025) - Ruiyuan Shi; Jiajian Liang; Chengbao Huang; Likai Hu; Lingyan Cheng; Zhao Tu; Xiaonan Wang; Jie Wang; Xiang Fang; Li Wang (Trends in Food Science & Technology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Epitaxial growth of wafer-scale PbS single-crystal films for room-temperature near-infrared sensing - Hao Zhu; Yao Wen; Ruiqing Cheng; Lei Yin; Yong Liu; Chao Jiang; Hao Wang; Ziren Xiong; Chuanyang Cai; Yangyuan Tu; Qisheng Wang; Long Fang; et al. (Science Bulletin, 2026)

Microseismic source localization method based on ABC-CS improved fusion algorithm - Wenfeng Tu; Chao Jia; Liping Li; Shuai Cheng; Diyang Chen; Yanhuan Zhang; Zhangcheng Yan; Feng Zhang (Acta Geophysica, 2026)

Experimental study on macro-meso damage of jointed rock mass under sequential cyclic loading–unloading followed by freeze–thaw cycles - Junhao Wei; Shili Hu; Zhengding Deng; Guanshi Wang; Qiang Cheng; Yaojie Tu (Transportation Geotechnics, 2026)

Corrigendum to “CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction” [Chem. Eng. J. 523 (2025) 168486] - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2026)

Performance of Spectral Indices and Machine Learning Algorithms in Seasonal Classification of Urban Impervious Surfaces from Sentinel-2 Imagery: A Case Study of Taipei - Alex Ssewanyana; Min-Cheng Tu (Remote Sensing in Earth Systems Sciences, 2026)

An unprecedented alternariol-zinnol hybrid and six undescribed zinnol derivatives from the phytopathogen Alternaria solani and their cytotoxic activities - Ming Hu; Run-Cheng Yan; Qiao-Ling Wei; Jiang-Li Su; Bi-Juan Yang; Wen-Chao Tu; Gan-Peng Li; Xing-De Wu (Phytochemistry, 2026)

Cyclic response analysis of suction anchors for floating wind turbine in clays under inclined loading - Wenbo Tu; Yaoyu Jia; Zhenhao Shi; Xiaoqiang Gu; Xinglei Cheng (Ocean Engineering, 2026)

Pore size of woven slit-film geotextiles subjected to unequal biaxial tensile strains obtained from wet sieving tests - Lin Tang; Kun Tu; Yi Cheng Hu; Wen Ming Shen; Yi Wang (Geotextiles and Geomembranes, 2026)

Study on the mechanism of flavor development in ultrasound-assisted microwave vacuum drying of shiitake mushrooms: Dosage effect of ultrasonic amplitude - Lujie Cheng; Hanbing Xiao; Dongkun Tu; Yingting Zhao; Yong Lin; Qisen Xiang; Yuting Tian (Food Chemistry, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Effects of warming and elevated CO2 on gross nitrogen dynamics and N2O emissions disappeared under combined treatment in waterlogged paddy soils - Xiaoshun Tu; Jing Wang; Xiaoyu Liu; Nyumah Fallah; Yves Uwiragiye; Yuanyuan Huang; Zucong Cai; Scott X. Chang; Yi Cheng; Christoph Müller (Agriculture, Ecosystems & Environment, 2026)

Carbon dioxide as the primary greenhouse gas emission in hard clam (Meretrix taiwanica) aquaculture - Yin-Yu Chen; Wei-Sheng Zhang; Chien‑Wei Tu; Bo-Ying Chen; Wen-Ping Cheng; Zhen Hao Liao; Yi-Jung Chen; Meng-Chou Lee; Fan-Hua Nan; Han-Yang Yeh (Aquaculture International, 2026)

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Optimizing the spatial configuration of scallop suspended cultivation net cages by leveraging seston flux variables based on the lattice Boltzmann hydrodynamics - Gangqin Tu; Haifei Liu; Zhiming Ru; Tao Sun; Wei Yang; Wei Huang; Li Cheng (Aquaculture, 2026)

Experimental analysis of a solar-driven modular latent heat storage system for ventilation air heating under real and dynamic meteorological conditions - Y. Ma; D.L. Deng; Y. Tao; Q.M. Du; Y. Wang; Y. Cheng; J.Y. Tu (Energy and Buildings, 2026)

Electrochemically activated polypyrrole for full-polymer electrochemical deionization: Unraveling potential-gated ion exchange behavior and its application to oxyanion removal - Hung-Yi Huang; Yi-Heng Tu; Yi-An Chen; Cheng-Wei Lin; Yu-Hung Cheng; Hsing-Mei Chou; Yu-Hsiang Yang; Yun Ku; Zhiyin Yang; Sophia Uemura; Hsin-Lung Chen; Richard B. Kaner; et al. (Chemical Engineering Journal, 2026)

Flexible-rigid coupling configuration for advanced energy-sensing integrated microsystems - Chang-Liu He; Yao Tan; Hao Zheng; Cheng Tu; Xin-Ran Zhang; Dong-Ming Fang; Xu Zeng; Xiao-Sheng Zhang (Chemical Engineering Journal, 2026)

Functional characterization of PsnErf1b in regulating salt stress tolerance in poplar - Zihan Cheng; Xinyu He; Xinyue Tu; Haiyan Fang; Lin Liu; Tingbo Jiang; Xuemei Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Motor Cortex VIP Interneurons Participate in Dexmedetomidine-Associated Sleep Modulation - Wei Wang; Hanmei Zhang; Tianqi Zhang; Qianyi Huang; Jiaxin Li; Nuo Li; Yue Xi; Xiaohan Yang; Fen Wang; Jun Tu; Dongmei Ji; Juan Cheng (Molecular Neurobiology, 2026)

Interannual relationship between the severity of summer cluster high-temperature events in Northwest China and the North Atlantic sea surface temperatures - Xinyu Yang; Botao Zhou; Xiaolu Zhang; Wenxin Xie; Yanbing Tu; Yang Cheng (Climate Dynamics, 2026)

Salient Object Detection Guided Fish Phenotype Segmentation in High-Density Underwater Scenes via Multi-Task Learning - Jiapeng Zhang; Cheng Qian; Jincheng Xu; Xueying Tu; Xuyang Jiang; Shijing Liu (Fishes, 2025)
Phenotyping technologies are essential for modern aquaculture, particularly for precise analysis of individual morphological traits. This study focuses on critical phenotype segmentation tasks for fish carcass and fins, which have significant applications in phenotypic assessment and breeding. In high-density underwater environments, fish frequently exhibit structural overlap and indistinct boundaries, making it difficult for conventional segmentation methods to obtain complete and accurate phenotypic regions. To address these challenges, a double-branch segmentation network is proposed for fish phenotype segmentation in high-density underwater scenes. An auxiliary saliency object detection (SOD) branch is introduced alongside the primary segmentation branch to localize structurally complete targets and suppress interference from overlapping or incomplete fish while inter-branch skip connections further enhance the model’s focus on salient targets and their boundaries. The network is trained under a multi-task learning framework, allowing the branches to specialize in edge detection and accurate region segmentation. Experiments on large yellow croaker (Larimichthys crocea) images collected under real farming conditions show that the proposed method achieves Dice scores of 97.58% for carcass segmentation and 88.88% for fin segmentation. The corresponding ASD values are 0.590 and 0.364 pixels, and the HD95 values are 3.521 and 1.222 pixels. The method outperforms nine existing algorithms across key metrics, confirming its effectiveness and reliability for practical aquaculture phenotyping.

Cassane diterpenoids with hepatic gluconeogenesis inhibitory activity from the seeds of Caesalpinia decapetala (Roth) Alston - De-Sheng Wang; Yu Shen; Lin-Fen Ding; Run-Cheng Yan; Ming Hu; Wen-Chao Tu; Liu-Dong Song; Suling Huang; Xing-De Wu (Phytochemistry, 2025)

Fabrication of Rubus chingii Hu ellagitannins-loaded W/O/W double emulsion gels stabilized by WPI/pectin complexes: Physicochemical properties, digestion characteristics, and transformation of ellagitannins - Dong-Jun Hou; Quan-yuan Xie; Ming-Shun Chen; Yu-Lin Cheng; Bing Zhang; Zong-cai Tu; Lu Zhang (Food Chemistry, 2025)

Geological and geochemical characteristics of intermediate-basic intrusions in Funiushan area, southern margin of the North China Craton: Implications for tectonic environment and mantle properties in the Early Cretaceous - Wei Zeng; Feng-Yue Sun; Cheng-Dong Li; Zhi-Dan Li; Yin-Hang Cheng; Wen-Gang Liu; Jia-Run Tu; Chao Zhang; Xing Liu; Wei-Zhi Sun (Lithos, 2025)

Integrated assessment of wind energy's emission and meteorological effects on PM2.5 in Taiwan - I-Chun Tsai; Pei-Rong Hsieh; Cheng-Wei Lin; Chung-Cheh Chou; Chia-Ying Tu; Chao-Tzuen Cheng; Huang-Hsiung Hsu (Journal of Environmental Management, 2025)

Isolation of largemouth bass virus (LMBV) and dominant immunogenic epitope screening of the major capsid protein of LMBV - Jie Leng; Ling-Yun Lin; Yun-Yao Tu; Cheng-Ke Zhu; Qun Lu; Ming-Ji Lv; Tao He; Jian-Yong Hu; Zhao-Fang Han; Song Zhu (Fish & Shellfish Immunology, 2025)

CNP-MoS2@HA nanocomposite promotes neurovascular recovery through sustained release and cell cycle navigation in neurogenic erectile dysfunction - Sen Fu; Peng Hu; Xiao-yu Zhu; Zheng-hui Jin; Hong-qi Zhao; Ming-tao Wu; Jia-xin Wang; Bei-ning Li; Li-da Ren; Bo-cheng Tu; Deng-jian-yi Xu; Hong-yang Jiang; et al. (Chemical Engineering Journal, 2025)

Investigating the interaction mechanism of five flavonoids and PD-L1 based on multi-spectroscopy and molecular dynamics - Yijie Cai; Yijun Tu; Hong Cheng; Jianqing Yu (Chemico-Biological Interactions, 2025)

Waste biomass-derived organic matter for sustainable soil remediation: Enhancing heavy metal removal and eluent reuse in agricultural application - Shuai Yang; Chen Tu; Guo-ming Liu; Yuan Li; Yi Wang; Xia Zhu; Shao-cheng Si; Run-lai Luo; Zhong-yuan Li; Yong-ming Luo (Bioresource Technology, 2025)

Geochemical characteristics and UPb chronology of detrital zircon in the Neogene Shizigou Formation, Qigequan area, western Qaidam Basin: Implications for tectonics, paleoclimate, and uranium sources - Chao Zhang; Shanbo Wang; Yinhang Cheng; Jiarun Tu; Reng’’an Yu; Ping Feng; Zhifeng Zuo; Yongliang Zang (Journal of Geochemical Exploration, 2025)

Investigation of the mechanism of H2O2 combined pulsed electric field treatment reducing the antigenicity of parvalbumin and tropomyosin by high-resolution mass spectrometry, molecular dynamics and DFT computation - Xiangfei Hu; Hui Wang; Qiannan Jiang; Pingwei Wen; Jie Cheng; Haibin Liu; Yueming Hu; Zongcai Tu (Innovative Food Science & Emerging Technologies, 2025)

Chelation of cerium (III) with fish skin collagen peptides: Improving the in vitro stability and bioavailability of inorganic cerium - Peihan Wu; Zongcai Tu; Hui Wang; Yueming Hu; Jie Cheng; Hai-bin Liu; Pingwei Wen (Food Research International, 2025)

Effects of airborne ultrasonic coupled microwave vacuum drying on moisture-heat migration and quality characteristics of shiitake mushrooms - Dongkun Tu; Lujie Cheng; Ye Xu; Yuxin Cheng; Yuhua Huang; Yingting Zhao; Qisen Xiang; Yuting Tian (Food Research International, 2025)

Identifying gelatin source by mass spectrometry: A review - Xiao-Mei Sha; Le-Ying Yang; Hui Wang; Jie Cheng; Hao-Sheng Luo; Li-Jun Zhang; Zi-Zi Hu; Zong-Cai Tu (Food Chemistry, 2025)

A fish-gelatin-modified multifunctional hydrogel with “salt-in-water” for dendrite-free flexible zinc-ion batteries - Wen-Long Cheng; Zi-Qiang Cheng; Zi-Zi Hu; Ming-Ming Hu; Guang-Xian Liu; Lin-Feng Yuan; Yan-Hui Fu; Xiao-Mei Sha; Zong-Cai Tu (Chemical Engineering Journal, 2025)

Vismodegib Potentiates Marine Antimicrobial Peptide Tilapia Piscidin 4-Induced Cytotoxicity in Human Non-Small Cell Lung Cancer Cells - Wei-Chen Yeh; Yun-Chieh Tu; Tzu-Cheng Chien; Pei-Ling Hsu; Chu-Wan Lee; Shih-Ying Wu; Bo-Syong Pan; Hsin-Hsien Yu; Bor-Chyuan Su (Probiotics and Antimicrobial Proteins, 2025)

Performance and mechanism of synchronous carbon and nitrogen removal from secondary effluent by denitrification coupled with partial-denitrification anammox - Qingfeng Cheng; Yanting Tu; Wenxing Zhao; Lichao Nengzi; Zhongyou Gong; Erdeng Du; Mingguo Peng (Journal of Cleaner Production, 2025)

Multi-Scale study on combustion acceleration and Self-Catalytic mechanisms of Nickel-Based energetic complex [Ni(N2H4)2](N3)2 - Cheng Dong; Shiyong Chen; Lixiao Shen; Tu Xu; Yinning Zeng; Yan Li; Zhenxin Yi; Chenguang Zhu; Lin Zhang; Shunguan Zhu (Fuel, 2025)

Overcoming the bottleneck in one-electron reduction of CO2 with mechanical energy-driven triboelectric plasma-enabled catalysis - Qinglong Ru; Bao Zhang; Sumin Li; Jiao Wang; Wei Jiang; Nannan Liu; Hui Hu; Yongcui Yang; Taifeng Liu; Qianhong Gao; Yifei Zhu; Yu Jia; et al. (Chemical Engineering Journal, 2025)

Microbiome catalog and dynamics of the Chinese liquor fermentation process - Xue Zhu; Liangqiang Chen; Pengshuo Yang; Sha Luo; Mengjing Teng; Wenjie Zhu; Yuxue Li; Dan Zhao; Nan Wang; Xiaoke Chen; Mingyue Cheng; Huabin Tu; et al. (Bioresource Technology, 2025)

Neolignans with anti-inflammatory activity from Piper kadsura (Choisy) Ohwi - Xingxing Liu; Yi Wen; Xilei Wang; Yan Qi; Wenhao Zhou; Yijun Tu; Jiachuan Lei; Hong Cheng; Jianqing Yu (Natural Product Research, 2025)

Valorization of solid digestate through biochar production for toluene adsorption and enhanced energy recovery as solid recovered fuel - Shao-Fu Tu; Yu-Ming Chu; Tse-Lun Chen; Hsing-Cheng Hsi; Hwong-wen Ma; Yu-Chieh Ting (Waste Management, 2025)

Multi-level ROS regulation to activate innate and adaptive immune therapies - Ke-Ke Feng; Cheng-Lei Li; Yi-Fan Tu; Shi-Cheng Tian; Rui Xiong; Bai-Sheng Sa; Jing-Wei Shao (Chemical Engineering Journal, 2025)

Multi-scale characteristics and statistically associated factors of ozone pollution in Hangzhou based on machine learning - Yu-ting He; Tao Ding; Ru Yi; Yuan-yuan Wang; Yi Fu; Cheng-kai Tu; Hong-yan Fang; Jin-ye Li; Ming Zhang (Atmospheric Pollution Research, 2025)

Facile fabrication of all-weather-available PDMS–CS/PVA–AgNWs@MS for efficient viscous crude oil recovery - Guojun Jiang; Chengbo Si; Jiahui Wang; Ji Yu; Saijie Tu; Mengxin Ye; Binyi Hu; Zhengwei Cheng; Yicheng Zhu; Sheng Xie (Journal of Water Process Engineering, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Functional lipid diversity and novel oxylipin identification for interspecies differentiation and nutritional assessment of commercial seahorse (Hippocampus) using untargeted and targeted lipidomics - Lijun Ge; Weibo Lu; Huixiang Wu; Jingjing Liang; Jie Liao; Keyun Cheng; Xi-xi Zeng; Si-wei Wang; Zejun Wang; Peiqing Mao; Zhujun Mao; Jing Xue; et al. (Food Chemistry, 2025)

Enhancing color conversion of perovskite quantum dot-based micro-light-emitting diodes via electrochemical etching and flow chemistry system - Wen-Tse Huang; Yen-Huei Lin; Po-Yi Tu; Loan Thi Ngo; Wei-Cheng Chen; Kai-Ling Liang; Yen-Hsiang Fang; Chaochin Su; Ru-Shi Liu (Chemical Engineering Journal, 2025)

GNSS-IR water level monitoring for complex environments: Application to Kalabeily Reservoir in Xinjiang, China - Peiyuan Wang; Rui Tu; Xiaolei Wang; Junqiang Han; Junjian Zhang; Fang Cheng; Xiaochun Lu (Advances in Space Research, 2025)

Endothelial USP11 drives VEGFR2 signaling and angiogenesis via PRDX2/c-MYC axis - Can Chen; Zilong Chen; Ruijie Luo; Wanheng Tu; Minwen Long; Minglu Liang; Min Cheng; Zhaohui Wang; Kai Huang; Cheng Wang (Angiogenesis, 2025)

Baicalin, a promising therapeutic drug against tilapia lake virus (TiLV) infection - Yun-Yao Tu; Jie Leng; Na Zhang; Qin Yang; Hong-Yu Tang; Cheng-Ke Zhu; Wei-Wei Zeng; Ming-Ji Lv; Song Zhu (Aquaculture, 2025)

Mechanistic exploration of activated carbon synergistic solar drying through theoretical analysis coupled with experimental validation - Binqi Rao; Taotao Zhao; Houde Tu; Yan Zhang; Shuying Yu; Shu Cheng; Qiang Sheng; Minrui Huang; Xilong Lu; Peng Xu; Fang Zhou (Waste Management, 2025)

Impact of 2,4-di-tert-butylphenol on pancreatic lipase activity in emulsions: Multispectral, molecular docking, and in vitro digestion analysis - Weiyan Guan; Juan Cheng; David Julian McClements; Zongcai Tu; Jing Chen; Da Ma (Food Chemistry, 2025)

Dust storm detection for ground-based stations with imbalanced machine learning - Shikang Du; Siyu Chen; Shanling Cheng; Jiaqi He; Dan Zhao; Xusheng Zhu; Lulu Lian; Xingxing Tu; Qinghong Zhao; Yue Zhang (Environmental Modelling & Software, 2025)

A Colorimetric/Fluorescence Dual Detection for Acid Phosphatase Based on Copper Nanoclusters - Yuanyuan Cheng; Xiujuan Huang; Yifeng Tu; Qi Ma; Jilin Yan (Journal of Fluorescence, 2025)

Sex differences in aristolochic acid I-induced nephrotoxicity in mice and the effect of estradiol - Qianru Wang; Jiuwen Hou; Fan Shui; Jia Tang; Jianjun Du; Cheng Chen; Wenjing Zhang; Maggie Shiliu Tu; Chunhui Li; Qibing Mei (Toxicology and Applied Pharmacology, 2025)

Revealing ionically isolated Li loss in practical rechargeable Li metal pouch cells - Xiangrui Duan; Yuanjian Li; Kai Huang; Shuibin Tu; Guocheng Li; Wenyu Wang; Hongyu Luo; Zihe Chen; Chunhao Li; Kai Cheng; Xin-Xin Wang; Li Wang; et al. (Science Bulletin, 2025)

Effect of scour-hole dimensions on the failure mechanism of suction caisson for offshore wind turbine in clay - Wenbo Tu; Daolong Shu; Xiaoqiang Gu; Xinglei Cheng; Yufan He; Shifang Ren (Ocean Engineering, 2025)

Synthesis and characterization of fish gelatin hydrogels for enhanced biopolymer applications - Wen-Long Cheng; Shan Shan; Sheng Shu; Guang-Xian Liu; Lin-Feng Yuan; Xiao-Mei Sha; Zong-Cai Tu (Food and Bioproducts Processing, 2025)

FSD1 inhibits glioblastoma diffuse infiltration through restriction of HDAC6-mediated microtubule deacetylation - Dake Xiao; Haowen Ran; Lishu Chen; Yuanyuan Li; Yan Cai; Songyang Zhang; Qinghui Qi; Huiran Wu; Cheng Zhang; Shuailiang Cao; Lanjuan Mi; Haohao Huang; et al. (Science China Life Sciences, 2025)
The infiltration of glioblastoma multiforme (GBM) is predominantly characterized by diffuse spread, contributing significantly to therapy resistance and recurrence of GBM. In this study, we reveal that microtubule deacetylation, mediated through the downregulation of fibronectin type III and SPRY domain-containing 1 (FSD1), plays a pivotal role in promoting GBM diffuse infiltration. FSD1 directly interacts with histone deacetylase 6 (HDAC6) at its second catalytic domain, thereby impeding its deacetylase activity on α-tubulin and preventing microtubule deacetylation and depolymerization. This inhibitory interaction is disrupted upon phosphorylation of FSD1 at its Ser317 and Ser324 residues by activated CDK5, leading to FSD1 dissociation from microtubules and facilitating HDAC6-mediated α-tubulin deacetylation. Furthermore, increased expression of FSD1 or interference with FSD1 phosphorylation reduces microtubule deacetylation, suppresses invasion of GBM stem cells, and ultimately mitigates tumor infiltration in orthotopic GBM xenografts. Importantly, GBM tissues exhibit diminished levels of FSD1 expression, correlating with microtubule deacetylation and unfavorable clinical outcomes in GBM patients. These findings elucidate the mechanistic involvement of microtubule deacetylation in driving GBM cell invasion and offer potential avenues for managing GBM infiltration.

Ultrasound-assisted microwave vacuum drying enhances flavor release during stewing of dried shiitake mushrooms - Dongkun Tu; Ye Xu; Yuxin Cheng; Yuhua Huang; Yingting Zhao; Yuting Tian (Food Chemistry, 2025)

Missing-linker defects of Ce-UiO-66 for enhanced radical scavenging efficiency and proton conductivity in proton exchange membrane fuel cells - Ziqiang Tu; Xuan He; Xing Du; Weixin Li; Daheng Wang; Wei Fang; Haijun Zhang; Hui Chen; Lei Zhao; Cheng Wang (Chemical Engineering Journal, 2025)

Mining of latent feruloyl esterase resources in rumen and insight into dual-functional feruloyl esterase-xylanase from Pecoramyces ruminantium F1 - Qicheng Shi; Jing Ma; Ahmed M. Abdel-Hamid; Yuqi Li; Pei Zhong; Dongyang Wang; Zhanying Sun; Tao Tu; Weiyun Zhu; Yanfen Cheng; Isaac Cann (Bioresource Technology, 2025)

FYB1-targeted modulation of CAPG promotes AML progression - Wenyuan Liu; Hongli Yin; Zhiwei Xie; Fang Fang; Jinhua Chu; Linhai Yang; Lingling Huang; Songji Tu; Huaju Cai; Zhengyu Wu; Anbang Wei; Chengzhu Liu; et al. (Molecular and Cellular Biochemistry, 2025)
Acute myeloid leukemia (AML) is a rare and heterogeneous disease. Over the past few decades, patient prognosis has improved with continuous improvements in treatment, but outcomes for some patients with primary drug resistance or relapse after treatment remain poor. Additional therapies to improve outcomes for these patients are urgently needed. FYB1 expression differs substantially between AML tissues and normal tissues. High FYB1 expression is correlated with poorer overall survival (OS), indicating that FYB1 may regulate AML progression. Therefore, understanding the effect of FYB1 on AML could improve the success rate of therapeutic approaches and prognosis for patients with AML. In this study, through analysis of large databases and both in vivo and in vitro experiments, we assessed the expression and role of FYB1 in AML and the relationship of FYB with patient prognosis. Downstream targets of the FYB1 gene were analyzed by RNA-seq. Database mining and in vitro experiments were used to further clarify the effect of the downstream target gelsolin-like actin-capping protein (CAPG) on AML cells and its relationship with patient prognosis. FYB1 expression was significantly higher in AML tissue and corresponded with a poor prognosis. FYB1 knockdown inhibited AML cell proliferation, promoted cell apoptosis, reduced cell adhesion capability and significantly reduced the tumor formation rate in mice. In addition, FYB1 knockdown induced a notable decrease in CAPG expression. The suppression of CAPG significantly inhibited cell proliferation and increased cell apoptosis. The conclusions of this study underscore the pivotal role of the FYB1/CAPG axis in promoting AML. We propose that the FYB1/CAPG axis could serve as a new thread in the development of therapeutic strategies for AML.

Year-round natural spawning, early ontogeny, and larval rearing of the painted sweetlips, Diagramma pictum (Thunberg, 1792) in a hatchery: Potential as a new species for mariculture - Pei-Sheng Chiu; Bo-Hong Yu; Yu-Hsin Tu; Yeong-Torng Chu; Cheng-Hsuan Huang; Shine-Wei Ho; Sun-Hon Lin; Shinn-Lih Yeh; Ming-Yih Leu (Aquaculture, 2025)

Potential prebiotic properties and proliferation mechanism of fermented milk-derived polypeptides - Lu Cheng; Feng Wang; Yuqiao Guo; Qiwei Du; Xiaoqun Zeng; Zhen Wu; Yuxing Guo; Maolin Tu; Daodong Pan (Food Chemistry, 2025)

An innovative dual-mode catalytic strategy for Boosting the Mineralization of organic pollutants through Dark-Light Cycle-Mediated Alternative Transformation pathways with NC/C3N4 in persulfate-based advanced oxidation process - Junjie Cheng; Xinman Tu; Xinding Lv; Li Zhang; Rentao Zhou; Shaohua Luo; Honghu Zeng; Tingting Li; Jianping Zou (Chemical Engineering Journal, 2025)

Fast single-crystallization of Cu foils facilitated by graphene growth - Xiaomeng Guo; Fangzhu Qing; Cheng Qian; Qinglong Zhu; Xiaoming Tu; Wanli Zhang; Feng Ding; Xuesong Li (Chemical Engineering Journal, 2025)

Unveiling the interaction and combined effects of multiple metals/metalloids exposure to TNF-α and kidney function in adults using bayesian kernel machine regression and quantile-based G-computation - Kuei-Hau Luo; Hung-Pin Tu; Yong-Chuan Chung; Min-Hsin Huang; Chen-Cheng Yang; Tzu-Hua Chen; Cheng-Hong Yang; Hung-Yi Chuang (Journal of Trace Elements in Medicine and Biology, 2024)

Comprehensive assessment of rice bran dietary fiber on gut microbiota composition and metabolism during in vitro fermentation - Jingni Cheng; Kai Ye; Chujing Fu; Yu Zhou; Yang Chen; Gaoxing Ma; Shiguo Chen; Jie Tu; Hang Xiao (Food Research International, 2024)

Non-coding RNA notations, regulations and interactive resources - Mengwei Cheng; Yinhuan Zhu; Han Yu; Linlin Shao; Yiming Zhang; Lanxing Li; Haohong Tu; Luyao Xie; Haoyu Chao; Peijing Zhang; Saige Xin; Cong Feng; et al. (Functional & Integrative Genomics, 2024)

Unravelling the nature differences of halide anions affecting the sorption of U(VI) by hydrous titanium dioxide supported waste polyacrylonitrile fibers in the presence of carbonates - Cheng Wang; Jun Liu; Bingtao Gui; Chao Li; Junxiang Shu; Shuwen An; Changsong Zhao; Juan Zhai; Ning Liu; Tu Lan (Science of The Total Environment, 2024)

Bioassay-guided isolation of antibacterial and anti-inflammatory components from Atractylodes lancea - Wenhao Zhou; Xiaoqin Zheng; Xilei Wang; Yinghan Tian; Yi Wen; Yijun Tu; Jiachuan Lei; Hong Cheng; Jianqing Yu (Phytochemistry, 2024)

Fabrication, characterization, and bioactivity of self-assembled carrier-free colloidal dispersions from Citrus × Limon ‘Rosso’ essential oil and tea polyphenols - Fangying Cheng; Mianhong Chen; Zhihao Duan; Ying Zou; Yunxia He; Fanke Zeng; Yuan Yuan; Tiaokun Fu; Hao Tu; Ruyi Li; Jihua Li; Wei Zhou (Food Chemistry, 2024)

MGDA-assisted plant washing agent for improving the removal of Cd and Cu from farmland soils - Yi Wang; Chen Tu; Yuan Li; Shuai Yang; Ying Liu; Xia Zhu; Shao-cheng Si; Run-lai Luo; Xiang-liang Pan; Yong-ming Luo (Environmental Pollution, 2024)

LiF-enriched interphase promotes Li+ desolvation and transportation enabling high-performance carbon anode under wide-range temperature - Wenbin Luo; Kuo Li; Tu Ran; Di Ma; Xingkun Chen; Haisong Wang; Yi Cheng; Xiaofei Yang (Chemical Engineering Journal, 2024)

A novel strategy employing lignin biochar to simultaneously promote remediation and safe crop production in Cd-contaminated soil - Yanying He; Baobin Mi; Cheng Luo; Honglin Tao; Xin Zhang; Jinwen Yu; Xueying Mo; Jian Hu; Long Chen; Naimei Tu; Fangfang Wu (Chemical Engineering Journal, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

TaSRT2 recognizes a viral protein to activate host immunity by increasing histone acetylation - Kaili Zhong; Yaoyao Jiang; Haichao Hu; Bowen Yuan; Mila Wu; Aizhu Tu; Gecheng Xu; Linna Cai; Tingting Liu; Shiqi Gao; Linzhi Li; Qiansheng Liao; et al. (Science Bulletin, 2024)

Characterizing formaldehyde emissions from forklifts in China based on real-world online measurements - Zeyan Wu; Manni Zhu; Yongxin Wu; Zhipeng Tu; Zhijiong Huang; Cheng Li; Wenqin Zhou; Xiaoliang Gui; Xueqin Zheng; Junyu Zheng (Atmospheric Environment, 2024)

Sustainability Assessment and Multi-angle Diagnosis of Regional Water Resources-Social Economy-Ecological Environment System Using a Novel TODIMSort with MS Clustering Algorithm - Yan Tu; Nengxin Wang; Linqi Cheng; Liyi Liu (Water Resources Management, 2024)

Comprehensive profiles of sulfur cycling microbial communities along a mangrove sediment depth - Lu Qian; Bozhi Yan; Jiayin Zhou; Yijun Fan; Mei Tao; Wengen Zhu; Cheng Wang; Qichao Tu; Yun Tian; Qiang He; Kun Wu; Mingyang Niu; et al. (Science of The Total Environment, 2024)

Controllable preparation of graphene glass fiber fabric towards mass production and its application in self-adaptive thermal management - Ruojuan Liu; Fan Yang; Shuting Cheng; Xianghe Yue; Fushun Liang; Wenjuan Li; Jingnan Wang; Qinchi Zhang; Liangyu Zou; Hao Yuan; Yuyao Yang; Kangyi Zheng; et al. (Science Bulletin, 2024)

Structurally diverse diterpenoids from the seeds of Caesalpinia minax Hance and their bioactivities - Wen-Chao Tu; Lin-Fen Ding; Liu-Dong Song; Yong-Jiao Li; Run-Cheng Yan; Yun Wu; Wei-Yang Feng; Xing-De Wu (Phytochemistry, 2024)

Incense-burning smoke ingredient Auramine enhances lincRNA-p21 expression for chemosensitization in p53-mutated non-small cell lung cancer - Hsuan-Yu Huang; Chia-Hung Chen; Fang-Ju Cheng; Bo-Wei Wang; Chih-Yen Tu; Yun-Ju Chen; Yu-Hao He; Chun-Hsu Yao; Wei-Chien Huang (Journal of Hazardous Materials, 2024)

Co-contamination and interactions of multiple mycotoxins and heavy metals in rice, maize, soybeans, and wheat flour marketed in Shanghai City - Zuoyin Zhu; Wenbo Guo; Haisheng Cheng; Hanke Zhao; Jie Wang; Mohamed F. Abdallah; Xinli Zhou; Hulong Lei; Weilong Tu; Hongyang Wang; Junhua Yang (Journal of Hazardous Materials, 2024)

Wave, flow, and suspended sediment dynamics under strong winds on a tidal beach - Lingpeng Meng; Junbiao Tu; Xiaodong Wu; Sha Lou; Jun Cheng; Sergey Chalov; Xiangju Han; Daidu Fan (Estuarine, Coastal and Shelf Science, 2024)

Incorporation of atomic Fe-oxide triggers a quantum leap in the CO2 methanation performance of Ni-hydroxide - Amisha Beniwal; Dinesh Bhalothia; Yin-Rong Chen; Jui-Cheng Kao; Che Yan; Nozomu Hiraoka; Hirofumi Ishii; Mingxing Cheng; Yu-Chieh Lo; Xin Tu; Yun-Wei Chiang; Chun-Hong Kuo; et al. (Chemical Engineering Journal, 2024)

Mechanisms insights into Cd passivation in soil by lignin biochar: Transition from flooding to natural air-drying - Yanying He; Baobin Mi; Cheng Luo; Wenjie Zhao; Yule Zhu; Long Chen; Naimei Tu; Fangfang Wu (Journal of Hazardous Materials, 2024)

Toward soil carbon storage: The influence of parent material and vegetation on profile-scale microbial community structure and necromass accumulation - Yu-Zhu Li; Xue-Lian Bao; Shi-Xin Tang; Ke-Qing Xiao; Cheng-Jun Ge; Hong-Tu Xie; Hong-Bo He; Carsten W. Mueller; Chao Liang (Soil Biology and Biochemistry, 2024)

Parent material influences soil properties to shape bacterial community assembly processes, diversity, and enzyme-related functions - Yu-Zhu Li; Xue-Lian Bao; Xue-Feng Zhu; Fang-Bo Deng; Ya-Li Yang; Yue Zhao; Hong-Tu Xie; Shi-Xin Tang; Cheng-Jun Ge; Chao Liang (Science of The Total Environment, 2024)

The phytochemistry, pharmacology, pharmacokinetics, quality control, and toxicity of Forsythiae Fructus: An updated systematic review - Jin-Jin Li; Zi-Hao Chen; Cheng-Jun Liu; Yu-Shuo Kang; Xin-Pu Tu; Hong Liang; Wei Shi; Feng-Xiang Zhang (Phytochemistry, 2024)

Re-melting of the Neoproterozoic juvenile mafic lower crust: The origin of adakitic and non-adakitic felsic suites in the southwest margin of Yangtze Craton - Jingkai Wu; Zhidan Zhao; Xiaowei Li; Xuejing Tu; Chen Li; Hangshan Lei; Qian Ma; Zhuang Miao; Yiyun Yang; Dong Liu; Qing Wang; Di-Cheng Zhu; et al. (Lithos, 2024)

A novel bifunctional particle electrode with abundant Fe/Fe3C and Fe-N-C sites to enhance the performance of electro-Fenton in degrading organic pollutant - Junjie Cheng; Xinman Tu; Li Zhang; Mingzhu Han; Rentao Zhou; Shaohua Luo; Honghu Zeng; Tingting Li; Jianping Zou (Journal of Environmental Chemical Engineering, 2024)

Towards multi-views cloud retrieval accounting for the 3-D structure collected by directional polarization camera - Haixiao Yu; Xiaobing Sun; Bihai Tu; Rufang Ti; Jinji Ma; Jin Hong; Cheng Chen; Xiao Liu; Honglian Huang; Zeling Wang; Safura Ahmad; Yi Wang; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

CuO NWs boosted triboelectric microfluidic nanosensor functionalized by collagen-protein interactions for real-time platelet count monitoring - Jia-Cheng Lin; Kuldeep Kaswan; Subhodeep Chatterjee; Yu-Wen Wu; Manish Kumar Sharma; Ashok Ranjan; Snigdha Roy Barman; Yu-Zih Lin; Thierry Burnouf; Wilfrid Boireau; Ming-Yen Lu; Yong-Kwang Tu; et al. (Chemical Engineering Journal, 2024)

Effects of Vitamin D Supplementation on Cognitive Outcomes: A Systematic Review and Meta-Analysis - Wen-Yin Chen; Ying-Chih Cheng; Chih-Chiang Chiu; Hsing-Cheng Liu; Ming-Chyi Huang; Yu-Kang Tu; Po-Hsiu Kuo (Neuropsychology Review, 2024)

C/N ratio of high-organic C materials is a poor predictor of microbial nitrate immobilization potential in a nitrate-rich soil: An 15N incubation study - Zhaoxiong Chen; Huimin Zhang; Xiaoshun Tu; Jing Wang; Ahmed S. Elrys; Quan Tang; Jinbo Zhang; Zucong Cai; Yi Cheng (Soil and Tillage Research, 2024)

Highly efficient thermal decomposition of AP through intimately encapsulating in 3DOM CoFe2O4 spinel - Desheng Yang; Chaofei Bai; Fengdan Zhu; Chang Liu; Cheng Zhao Tu; Guoping Li; Yunjun Luo; Tianfu Zhang (Chemical Engineering Journal, 2024)

Understanding seasonal cycle of daily extreme temperatures based on generalized additive model for location, scale and shape with smoothing spline - Kai Tu; Zhongwei Yan; Cheng Qian (International Journal of Climatology, 2024)
The seasonal cycle (SC) of surface air temperature is a substantial element in climatology. Some basic and important topics in climate change studies are based on accurate and reliable estimation of SCs, such as percentile‐based indices of extremes and probability density function (PDF) changes of daily temperatures. For both of them, most studies characterized SCs using averages of multi‐days windows, which is not smooth and accurate enough representing the extreme thresholds and climatological normal of SCs. It is necessary to construct smooth and reasonable SCs for more accurate estimation of temperature changes on extreme thresholds and PDFs. In this study, we propose a flexible method based on generalized additive models for location scale and shape and penalized b‐spline smoothing technique with respective distributions to construct smooth SCs and SC for extreme temperatures (SCETs). The accuracy of the constructed smooth SCETs is good with the estimation biases of percentiles tending to be zero. The constructed smooth SCET also exhibits good stability over time, such that the magnitude changes of temperatures on each calendar day are close to climatic changes of mean temperature when the concerned period shifts. Based on the constructed smooth SCs, climatic changes by seasons and PDFs between two periods, 1961–1990 and 1991–2020, are examined over China. The increase of thresholds for hot extremes in spring during the recent period is prominent, while the increase of thresholds for daytime cold extremes in summer over a part of central to southern China is also notable. The smooth SCs and SCETs based on our flexible statistical modelling framework can characterize daily extreme temperatures reasonably and accurately, and should be expected to have more applications for a better understanding of climate changes related to distributions and seasonal cycles.

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Study of a triple bottom line perspective to reach a sustainable development model for critical minerals using financial development - Cheng Liu; Guanying Dai; Hong Tu (Resources Policy, 2024)

Health risk assessment and potential sources of metals in riparian soils of the Wujiang River, China - Shenwen Cai; Ziwei Shen; Shaoqi Zhou; Qinghe Wang; Junwei Cheng; Xiong Yan; Mingjie Tan; Guojing Tu; Yi Cen (Environmental Geochemistry and Health, 2024)

Awakening soil microbial utilization of nitrate by carbon regulation to lower nitrogen pollution - Quan Tang; Jing Wang; Miaomiao Cao; Zhaoxiong Chen; Xiaoshun Tu; Ahmed S. Elrys; Hang Jing; Xiaozhi Wang; Zucong Cai; Christoph Müller; Tim J. Daniell; Xiaoyuan Yan; et al. (Agriculture, Ecosystems & Environment, 2024)

Additive-free electroless deposition on graphene/copper foil: Photo-induced and defect-assisted approach for environmentally friendly plating - Hsiao-Chien Chen; Abdul Shabir; Kun-Hua Tu; Cher Ming Tan; Wei-Hao Chiu; Ruei-Cheng Fan; Nilim Akash Baruah (Journal of Environmental Chemical Engineering, 2024)

The biochemical behavior and mechanism of uranium(Ⅵ) bioreduction induced by natural Bacillus thuringiensis - Shunzhang Chen; Junyuan Gong; Yanxia Cheng; Yuqi Guo; Feize Li; Tu Lan; Yuanyou Yang; Jijun Yang; Ning Liu; Jiali Liao (Journal of Environmental Sciences, 2024)

PDA-mediated colorimetric-fluorescence co-enhanced immunochromatography assay for the simultaneous and rapid detection of SARS-CoV-2 and HAdV - Xingsheng Yang; Xiaodan Cheng; Zhijie Tu; Hongjuan Wei; Zhen Rong (Chemical Engineering Journal, 2024)

Directing the persulfate activation reaction pathway by control of Fe-Nx/C single-atom catalyst coordination - Junjie Cheng; Xinman Tu; Pengxuan Wu; Rentao zhou; Shaohua Luo; Li Zhang; Jianping Zou; Yanhong Li; Hannah M. Johnson; Qiang Zhang (Chemical Engineering Journal, 2024)

Signaling pathways involved in microbial indoor air pollutant 3-methyl-1-butanol in the induction of stomatal closure in Arabidopsis - Tu-Trinh Thi Truong; Chi-Chou Chiu; Pei-Yu Su; Jing-Yu Chen; Tri-Phuong Nguyen; Masaru Ohme-Takagi; Ruey-Hua Lee; Wan-Hsing Cheng; Hao-Jen Huang (Environmental Science and Pollution Research, 2024)

Effects of field-aging on the impact of biochar on herbicide fate and microbial community structure in the soil environment - Hongguang Cheng; Dan Xing; Gratien Twagirayezu; Shan Lin; Shangyi Gu; Chenglong Tu; Paul W. Hill; David R. Chadwick; Davey L. Jones (Chemosphere, 2024)

Soil deformation and failure analysis of suction caisson in marine clay under combined loading - Wenbo Tu; Yuanhang Tu; Linya Liu; Xiaoqiang Gu; Pengfei Zhang; Xinglei Cheng (Ocean Engineering, 2024)

Green N1 additive modified perovskite precursor enables effective manufacturing of large-area solar cell modules with high efficiency and stability - Yue Zang; Yibo Tu; Chuanjia Jiao; Wangnan Li; Peng Zhou; Jiahao Cheng; Gaoyuan Yang; Tianxiang Shao; Jingchuan Ye; Guodong Li; Liang Chu; Shaojian Lu; et al. (Chemical Engineering Journal, 2024)

Efficient piezo-photocatalysis of Bi2O2(OH)NO3/BiOI heterojunction: Collaboration of piezoelectric polarization and interface electric field - Yuanrui Li; Xiaolei Zhang; Rui Sha; Tong Li; Cheng Hu; Shuchen Tu; Fang Chen; Hongwei Huang (Chemical Engineering Journal, 2024)

Edible electrospun zein nanofibrous scaffolds close the gaps in biofilm formation ability between microorganisms - Meng-Xin Hu; Fei He; Cheng-Kai Tu; Zhe-Xin Chen; Hui Teng; Xin Shao; Ge-Rui Ren; Ya-Xin Guo (Food Bioscience, 2023)

Eight novel brominated flame retardants in indoor and outdoor dust samples from the E-waste recycling industrial park: Implications for human exposure - Yongyin Lan; Yuxian Liu; Yanpeng Cai; Qingping Du; Hongkai Zhu; Haitao Tu; Jingchuan Xue; Zhipeng Cheng (Environmental Research, 2023)

Monocarboxylate transporter blockage-enabled lactate redistribution reshapes immunosuppressive tumor microenvironment and enhances chemodynamic immunotherapy - Jingxue Wang; Weixi Jiang; Mingxiao Fang; Chier Du; Xun Guo; Xiaoling Qiu; Xiaoting Wang; Yuanli Luo; Peng Tu; Chen Cheng; Pan Li; Haitao Ran; et al. (Chemical Engineering Journal, 2023)

Improving Blood Monocyte Energy Metabolism Enhances Its Ability to Phagocytose Amyloid-β and Prevents Alzheimer’s Disease-Type Pathology and Cognitive Deficits - Zhi-Hao Liu; Yu-Di Bai; Zhong-Yuan Yu; Hui-Yun Li; Jie Liu; Cheng-Rong Tan; Gui-Hua Zeng; Yun-Feng Tu; Pu-Yang Sun; Yu-Juan Jia; Jin-Cai He; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2023)

Analysis of bucket foundation installation in clay considering soil large deformation - Wenbo Tu; Yufan He; M. Hesham El Naggar; Linya Liu; Xiaoqiang Gu; Xinglei Cheng (Ocean Engineering, 2023)

Effects of tillage patterns and stover mulching on N2O production, nitrogen cycling genes and microbial dynamics in black soil - Da-Cheng Hao; Xing-Yuan Su; Hong-Tu Xie; Xue-Lian Bao; Xu-Dong Zhang; Lian-Feng Wang (Journal of Environmental Management, 2023)

Shiitake polysaccharides acted as a non-competitive inhibitor to α-glucosidase and inhibited glucose transport of digested starch from Caco-2 cells monolayer - Juncai Tu; Benu Adhikari; Margaret Anne Brennan; Weidong Bai; Ping Cheng; Charles Stephen Brennan (Food Research International, 2023)

Weak force-polarization driven exceptional piezo-photocatalysis by coupling dual-active piezoelectric semiconductors in NaNbO3/g-C3N4 heterojunction - Lina Guo; Cheng Hu; Shuchen Tu; Chongchen Wang; Lefu Mei; Yihe Zhang; Hongwei Huang (Chemical Engineering Journal, 2023)

Geochemical relationship and profile distribution of Selenium and Cadmium in typical Selenium-enriched areas in Enshi - Chengfeng Jiang; Wei Zhou; Liangzhe Yang; Jiali Yan; Shuxin Tu; Yuan Yuan; Dan Wang; Hao Cheng (Chemosphere, 2023)

Graphene oxide-based colorimetric/fluorescence dual-mode immunochromatography assay for simultaneous ultrasensitive detection of respiratory virus and bacteria in complex samples - Xiaodan Cheng; Xingsheng Yang; Zhijie Tu; Zhen Rong; Chongwen Wang; Shengqi Wang (Journal of Hazardous Materials, 2023)

Flexural behavior and design methodology for bamboo scrimber-aluminum plate composite beams - Ye Sheng; Defeng Tu; Feiyu Liao; Yuxing Yang; Chenggen He; Wei Zhang; Cheng Meng (Engineering Structures, 2023)

Harnessing Ag2S quantum dots with immune adjuvant for NIR-II fluorescence imaging-guided sonodynamic immunotherapy of colon cancer - Yuanyuan Zhang; Yujie Zhang; Yonghong Li; Yuhan Fu; Yuanru Zhao; Wei Zhao; Runqing Li; Yao Xian; Kangsheng Tu; Feng Wu; Cheng Li; Yuzhu Hou; et al. (Chemical Engineering Journal, 2023)

Enhancing catalytic activity and pore structure of metal–organic framework-808 via ligand competition for biodiesel production from microalgal lipids at reduced temperatures - Lei Qian; Jun Cheng; Kai Xin; Hao Guo; Yuxiang Mao; Jiacan Tu; Weijuan Yang (Bioresource Technology, 2023)

Intra-host mutation rate of acute SARS-CoV-2 infection during the initial pandemic wave - Kim El-Haddad; Thamali M. Adhikari; Zheng Jin Tu; Yu-Wei Cheng; Xiaoyi Leng; Xiangyi Zhang; Daniel Rhoads; Jennifer S. Ko; Sarah Worley; Jing Li; Brian P. Rubin; Frank P. Esper (Virus Genes, 2023)

Heterogeneous ultra-thin FeCo-LDH@Co(OH)2 nanosheets facilitated electrons transfer for oxygen evolution reaction - Xian Yang; Jun Cheng; Yang Xu; Hao Li; Weifeng Tu; Junhu Zhou (Chemical Engineering Journal, 2023)

Elucidating the role of T-cell exhaustion-related genes in colorectal cancer: a single-cell bioinformatics perspective - Wei Tu; Yan Tu; Chunhong Tan; Honghong Zhong; Sheng Xu; Jun Wang; Lv Huang; Ling Cheng; Haoguang Li (Functional & Integrative Genomics, 2023)

Target-triggered Fe3O4@NPC-UCNPs assembly for photoactivatable biosensing of Aflatoxin B1 - Zhou Xu; Shaoyi Yu; Xinyi Xie; Qingxia Li; Li Ding; Maolong Chen; Jia Tu; Keyu Xing; Yunhui Cheng (Chemical Engineering Journal, 2023)

Conductivity characteristics of landslide considering porosity, saturation, temperature and ion concentration - Bo-bo Xiong; Shi-jie Yang; Bing-qin Zhao; Xiao-chun Lu; Bin Tian; Cheng Li; Xuan-xuan Wu; Xiao-long Tu (Journal of Mountain Science, 2023)

Identification of Large Yellow Croaker under Variable Conditions Based on the Cycle Generative Adversarial Network and Transfer Learning - Shijing Liu; Cheng Qian; Xueying Tu; Haojun Zheng; Lin Zhu; Huang Liu; Jun Chen (Journal of Marine Science and Engineering, 2023)
Variable-condition fish recognition is a type of cross-scene and cross-camera fish re-identification (re-ID) technology. Due to the difference in the domain distribution of fish images collected under different culture conditions, the available training data cannot be effectively used for the new identification method. To solve these problems, we proposed a new method for identifying large yellow croaker based on the CycleGAN (cycle generative adversarial network) and transfer learning. This method constructs source sample sets and target sample sets by acquiring large yellow croaker images in controllable scenes and actual farming conditions, respectively. The CycleGAN was used as the basic framework for image transformation from the source domain to the target domain to realize data amplification in the target domain. In particular, IDF (identity foreground loss) was used to optimize identity loss judgment criteria, and MMD (maximum mean discrepancy) was used to narrow the distribution between the source domain and target domain. Finally, transfer learning was carried out with the expanded samples to realize the identification of large yellow croaker under varying conditions. The experimental results showed that the proposed method achieved good identification results in both the controlled scene and the actual culture scene, with an average recognition accuracy of 96.9% and 94%, respectively. These provide effective technical support for the next steps in fish behavior tracking and phenotype measurement.

Modeling of swimming posture dynamics for a beaver-like robot - Gang Chen; Wang Peng; Zhenyu Wang; Jiajun Tu; Huosheng Hu; Donghai Wang; Hao Cheng; Lvyuan Zhu (Ocean Engineering, 2023)

Developing the mathematical model to predict the nitrogen removal and N2O emission by the biological aerated filter - Qianqian Tu; Yiyihui Hong; Yinying Zhu; Hong Cheng; Xiaoliu Huangfu; Qiang He (Journal of Water Process Engineering, 2023)

Applicability of carbonate clumped isotope thermometry in the Tuchang-Jentse geothermal field - Yi-Chia Lu; Sheng-Rong Song; Ling-Wen Liu; Tsung-Ren Peng; Bill Bing-Cheng Chen; Remy Kai-Cheng Tu; Li-Hung Lin; Pei-Ling Wang (Geothermics, 2023)

Zeolitic imidazolate framework (ZIF-8)-derived acid-base bifunctional single-atom catalysts with Zn-Nx coordination for microalgal lipids conversion - Yuxiang Mao; Jun Cheng; Hao Guo; Lei Qian; Yang Xu; Jiacan Tu; Weijuan Yang (Fuel, 2023)

Photoperiod and gravistimulation-associated Tiller Angle Control 1 modulates dynamic changes in rice plant architecture - Hong Wang; Ranran Tu; Zheyan Ruan; Chi Chen; Zequn Peng; Xingpeng Zhou; Lianping Sun; Yongbo Hong; Daibo Chen; Qunen Liu; Weixun Wu; Xiaodeng Zhan; et al. (Theoretical and Applied Genetics, 2023)

Acidic polysaccharides from black ear and silver ear mushrooms modulated the release and transport of glucose from gelatinised sorghum starch during digestion - Juncai Tu; Benu Adhikari; Margaret Anne Brennan; Siyuan Luo; Ping Cheng; Weidong Bai; Charles Stephen Brennan (Food Chemistry, 2023)

Self-supported N-doped hierarchical Co3O4 electrocatalyst with abundant oxygen vacancies for acidic water oxidation - Xian Yang; Jun Cheng; Hao Li; Yang Xu; Weifeng Tu; Junhu Zhou (Chemical Engineering Journal, 2023)

SIRT4 in ageing - Ling He; Qingcheng Liu; Jielong Cheng; Mei Cao; Shuaimei Zhang; Xiaolin Wan; Jian Li; Huaijun Tu (Biogerontology, 2023)

pH-induced complex coacervation of fish gelatin and carboxylated chitosan: Phase behavior and structural properties - Chen Cheng; Zongcai Tu; Hui Wang (Food Research International, 2023)

Interactions between sorghum starch and mushroom polysaccharides and their effects on starch gelatinization and digestion - Juncai Tu; Benu Adhikari; Margaret Anne Brennan; Ping Cheng; Weidong Bai; Charles Stephen Brennan (Food Hydrocolloids, 2023)

Comprehensive analysis of arachidonic acid metabolism-related genes in diagnosis and synovial immune in osteoarthritis: based on bulk and single-cell RNA sequencing data - Bizhi Tu; Run Fang; Zheng Zhu; Guang Chen; Cheng Peng; Rende Ning (Inflammation Research, 2023)

AIseed: An automated image analysis software for high-throughput phenotyping and quality non-destructive testing of individual plant seeds - Keling Tu; Weifeng Wu; Ying Cheng; Han Zhang; Yanan Xu; Xuehui Dong; Mang Wang; Qun Sun (Computers and Electronics in Agriculture, 2023)

Preparation and characterization of carboxymethyl chitosan/pullulan composite film incorporated with eugenol and its application in the preservation of chilled meat - Zhen Zeng; Yu-Jing Yang; Qian Tu; Yu-Ying Jian; Da-Ming Xie; Ting Bai; Shan-Shan Li; Yun-Tao Liu; Cheng Li; Cai-Xia Wang; Ai-Ping Liu (Meat Science, 2023)

Dynamic response analysis of monopile offshore wind turbines to seismic and environmental loading considering the stiffness degradation of clay - Xinglei Cheng; Tianju Wang; Jianxin Zhang; Piguang Wang; Wenbo Tu; Wenqian Li (Computers and Geotechnics, 2023)

Model test and numerical simulation research on the mechanical response law of lager span and small interval tunnels constructed by CD method - Liping Li; Hongyun Fan; Hongliang Liu; Shangan Li; Shuai Cheng; Qihua Zhang; Wenfeng Tu; Shen Zhou (Tunnelling and Underground Space Technology, 2023)

Unusual uranium biomineralization induced by green algae: Behavior investigation and mechanism probe - Yanxia Cheng; Ting Zhang; Shunzhang Chen; Feize Li; Renwei Qing; Tu Lan; Yuanyou Yang; Jiali Liao; Ning Liu (Journal of Environmental Sciences, 2023)

Exploring consumer perception and acceptance of recycled merchandise under five-sense design - Jui-Che Tu; Cheng-Hsueh Yang; Sheng-Huei Lin; Kharisma Creativani (Environment, Development and Sustainability, 2023)

Corrigendum to “Comparative efficacy of omega-3 polyunsaturated fatty acids on major cardiovascular events: A network meta-analysis of randomized controlled trials” [Progress in Lipid Research. 2022 Oct 28;88:101196. doi: 10.1016/j.plipres.2022.101196] - Bo Yang; Ping-Tao Tseng; Xiang Hu; Bing-Yan Zeng; Jane Pei-Chen Chang; Yang Liu; Wei-Jie Chu; Shuang-Shuang Zhang; Zhi-Liang Zhou; Chih-Sheng Chu; Cheng-Ho Chang; Yu-Kang Tu; et al. (Progress in Lipid Research, 2023)

Advances in coastal ocean boundary layer detection technology and equipment in China - Haitao Zheng; Youwen Sun; Tao Luo; Xueling Cheng; Shiyong Shao; Shouyin Zheng; Bangyi Tao; Bin Chen; Qianguang Tu; Kan Huang; Bingbing Wang; Mian Wang; et al. (Journal of Environmental Sciences, 2023)

Electroreduction of nitrate to ammonia on atomically-dispersed Cu-N4 active sites with high efficiency and stability - Jun Cheng; Weifu Sun; Guorun Dai; Xian Yang; Rongxin Xia; Yang Xu; Xiao Yang; Weifeng Tu (Fuel, 2023)

O-hetero-Fe-N3.6 active sites in ZIF-derived carbon nanotubes for the electrocatalytic oxygen evolution reaction - Xian Yang; Jun Cheng; Xiao Yang; Yang Xu; Hao Li; Weifu Sun; Weifeng Tu; Junhu Zhou (Chemical Engineering Journal, 2023)

Tailored fabrication of quasi-isoporous and double layered α-Fe2O3 thin films and their application in photovoltaic devices - Shanshan Yin; Yuqin Zou; Manuel A. Reus; Xinyu Jiang; Suo Tu; Ting Tian; Ruoxuan Qi; Zhuijun Xu; Suzhe Liang; Yajun Cheng; Julian E. Heger; Matthias Schwartzkopf; et al. (Chemical Engineering Journal, 2023)

Effective interfacial energy band engineering strategy toward high-performance triboelectric nanogenerator - Xinkai Xie; Yuxiao Fang; Cheng Lu; Yi Tao; Li Yin; Yibo Zhang; Zixin Wang; Shiyan Wang; Jianwen Zhao; Xin Tu; Xuhui Sun; Eng Gee Lim; et al. (Chemical Engineering Journal, 2023)

Mechanisms of Coal and Gas Outburst Experiments: Implications for the Energy Principle of Natural Outbursts - Yang Lei; Yuanping Cheng; Liang Wang; Ting Ren; Qingyi Tu (Rock Mechanics and Rock Engineering, 2023)

A shift from nitrification to denitrification-dominated N2O emission in an acidic soil following organic amendment - Jing Wang; Qiao Huang; Yong Li; Xiaoshun Tu; Zhaoxiong Chen; Ahmed S. Elrys; Yi Cheng; Lifeng Ma (Biology and Fertility of Soils, 2023)

Low-Cd wheat varieties and soil Cd safety thresholds for local soil health management in south Jiangsu province, east China - Pengjie Hu; Feng Tu; Simin Li; Yunjun Pan; Cheng Kong; Xumei Zhang; Shaohua Wang; Yongquan Sun; Dan Qiu; Longhua Wu; Yongming Luo; Peter Christie (Agriculture, Ecosystems & Environment, 2023)

Isolation, Identification and Characteristic Analysis of Plant Endophyte Electrogenic Bacteria Shinella zoogloeoides SHE10 - Lijun Ling; Hong Luo; Zibin Li; Caiyun Yang; Mingmei Pang; Yixin Tu; Wenting Cheng; Kunling Jiang; Lu Lu (Current Microbiology, 2022)

Distinctive Roles of Wnt Signaling in Chondrogenic Differentiation of BMSCs under Coupling of Pressure and Platelet-Rich Fibrin - Baixiang Cheng; Fan Feng; Fan Shi; Jinmei Huang; Songbai Zhang; Yue Quan; Teng Tu; Yanli Liu; Junjun Wang; Ying Zhao; Min Zhang (Tissue Engineering and Regenerative Medicine, 2022)

Association of cognitive impairment and reduced cortical thickness in prefrontal cortex and anterior cingulate cortex with treatment-resistant depression - Mu-Hong Chen; Wan-Chen Chang; Pei-Chi Tu; Wei-Chen Lin; Cheng-Ta Li; Wen-Sheng Huang; Ya-Mei Bai; Shih-Jen Tsai; Tung-Ping Su (Brain Imaging and Behavior, 2022)

Impact of CT-Based and MRI-Based Attenuation Correction Methods on 18 F-FDG PET Quantification Using PET Phantoms - Cheng-Han Wu; Chun-Yuan Tu; Li-Chen Shen; Yueh-Hsun Lu; Bang-Hung Yang (Journal of Medical and Biological Engineering, 2022)

Effects of Chemotherapy on Neuroinflammation, Neuronal Damage, Neurogenesis, and Behavioral Performance in Bone Marrow Transplantation Recipient Mice - Zhong-Yuan Yu; Man-Yu Xu; Zhi-Hao Liu; Gui-Hua Zeng; Huan Fan; Cheng-Rong Tan; Yun-Feng Tu; Xian-Le Bu; Yan-Jiang Wang (Neurotoxicity Research, 2022)

New Insights into Failure Behaviors of Tectonic Coal Under Triaxial Conditions Using Reconstituted Coal Specimens - Jia Lin; Yuanping Cheng; Ting Ren; Qingquan Liu; Qingyi Tu (Rock Mechanics and Rock Engineering, 2022)

Study on the improvement of disaster resistance against tsunamis at Taiwan’s Keelung Port - Chih-peng Wang; Ban-jwu Shih; Min-cheng Tu (Natural Hazards, 2022)

Swimming behaviour of silver carp ( Hypophthalmichthys molitrix ) in response to turbulent flow induced by a D ‐cylinder - Senfan Ke; Zhiying Tu; Elsa Goerig; Junjun Tan; Bixin Cheng; Zhimin Li; Xiaotao Shi (Journal of Fish Biology, 2022)
Turbulence is a complex hydraulic phenomenon which commonly occurs in natural streams and fishways. Riverine fish are subjected to heterogeneous flow velocities and turbulence, which may affect their movements and ability to pass the fishways. However, studies focusing on fish response to turbulent flows are lacking for many species. Here we investigate the effects of the turbulence created by a vertical half‐cylinder of various diameters (1.9, 2.5, 3.2 and 5.0 cm) on the swimming ability and behaviour of silver carp, Hypophthalmichthys molitrix . The large D‐cylinders (3.0 and 5.0 cm) create specific vorticity and reduced velocities areas in their vicinity, which favours flow refuging behaviours (FRBs) and thus increased relative critical swimming speeds ( U rcrit , BL/s) of silver carp, by comparison to free‐flow conditions and cylinders of smaller diameter (1.9 and 2.5 cm). The flow speed at which silver carp maximized FRBs such as Karman gaiting downstream of the cylinder, holding position in the bow wake or entraining on the side ranged from 40 to 70 cm s −1 , depending on fish body size. When holding station near a cylinder under optimal flow speeds, the distance between the fish and the cylinder is related to the size of the fish, but also to the size of the cylinder and the produced vortices. The optimal holding region in the drag wake of the cylinder ranged from 28 to 40 cm downstream of the centre of the cylinder, depending on the size of the fish. Smaller fish, however, tend to use the reduced velocities areas located in the bow wake of the large cylinders. We hypothesize that fish will display FRBs, including maintaining a Karman gait in turbulent flow, when the ratio of the cylinder diameter to their body length is between 1:3 and 1:4. They also match their tail beat frequency to the vortex shedding frequency of the cylinder. Our results provide a better understanding of how silver carp respond to turbulent flows around physical structures, with implications for the design of nature‐like fishways or exclusion devices in both its native and invasive ranges.

Distribution of Coomassie Blue Stainable Particles in the Pearl River Estuary, China, Insight Into the Nitrogen Cycling in Estuarine System - Cui-Ci Sun; Wei-Zhong Yue; You-Shao Wang; Wei-Hong He; Yi-Guo Hong; Fu-Lin Sun; Hao Cheng; Mei-Lin Wu; Zhao-Yu Jiang; Fei Jiao; Yu-Tu Wang (Frontiers in Marine Science, 2022)
Distributions of Coomassie Blue stainable particles (CSP), the sources and transports, as well as their implications for nitrogen biogeochemical cycles in the Pearl River estuary (PRE) were investigated during two cruises in August 2016 and January 2017. CSP color concentrations (CSP concentration determined spectrophotometrically) were 73.7–685.3 μg BSA eq L –1 [μg Bovine serum albumin (BSA) equivalent liter –1 ] in August 2016 and 100.6–396.4 μg BSA eq L –1 in January 2017, respectively. CSP concentrations were high in low-salinity waters (<5), and declined from the river to the middle estuary by 80% in the wet season and 55.6% in the dry season, respectively, then increased again in the lower estuary due to high primary production. CSP concentrations were mainly associated with chlorophyll a (Chl a ) concentration except for the turbid mixing zone, suggesting that autochthonous phytoplankton production served as the primary source of CSP in the PRE. The concentrations of nitrogen (N) as CSP in the PRE were comparable to the nitrogen content of particulate hydrolysable amino acids (PHAA). Pictures of CSP taken by microscopy and the correlation between composition of PHAA and the ratio of Chl a /CSP color showed that CSP were relatively degraded due to delivery of old terrestrial protein to river section and extensive microbial degradation during mixing at the upper and middle parts of the estuary, whereas CSP in lower estuary appeared to be more labile due to higher fresh algal production. The contribution of CSP nitrogen (CSP-N) to the particulate nitrogen (PN) pool was 34.98% in summer and 30.8% in winter. The conservative estimate of CSP-N input flux in the Pearl River Delta was about 6 × 10 6 mol N d –1 . These results suggested that CSP was a significant pool of organic nitrogen in the PRE. The study of CSP composition in terms of nitrogen provides new insight into the roles of CSP on nitrogen biogeochemical processes in the turbid and productive estuarine system.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Experimental Investigation on the Mechanism of Coal and Gas Outburst: Novel Insights on the Formation and Development of Coal Spallation - Yang Lei; Yuanping Cheng; Ting Ren; Qingyi Tu; Yixuan Li; Longyong Shu (Rock Mechanics and Rock Engineering, 2021)

BnA1.CER4 and BnC1.CER4 are redundantly involved in branched primary alcohols in the cuticle wax of Brassica napus - Jie Liu; Lixia Zhu; Benqi Wang; Huadong Wang; Imran khan; Shuqin Zhang; Jing Wen; Chaozhi Ma; Cheng Dai; Jinxing Tu; Jinxiong Shen; Bin Yi; et al. (Theoretical and Applied Genetics, 2021)

Pulmonary Exposure to Copper Oxide Nanoparticles Leads to Neurotoxicity via Oxidative Damage and Mitochondrial Dysfunction - Hongmei Zhou; Ling Yao; Xuejun Jiang; Golamaully Sumayyah; Baijie Tu; Shuqun Cheng; Xia Qin; Jun Zhang; Zhen Zou; Chengzhi Chen (Neurotoxicity Research, 2021)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

A mitochondria-localized pentatricopeptide repeat protein is required to restore hau cytoplasmic male sterility in Brassica napus - Huadong Wang; Qing Xiao; Chao Wei; Hui Chen; Xiaohan Chen; Cheng Dai; Jing Wen; Chaozhi Ma; Jinxing Tu; Tingdong Fu; Jinxiong Shen; Bin Yi (Theoretical and Applied Genetics, 2021)

Reduction of OsMPK6 activity by a R89K mutation induces cell death and bacterial blight resistance in rice - Dongfei Wang; Hong Wang; Qunen Liu; Ranran Tu; Xingpeng Zhou; Yingxin Zhang; Weixun Wu; Ping Yu; Daibo Chen; Xiaodeng Zhan; Liyong Cao; Shihua Cheng; et al. (Plant Cell Reports, 2021)

Bi-allelic BRWD1 variants cause male infertility with asthenoteratozoospermia and likely primary ciliary dyskinesia - Ting Guo; Chao-Feng Tu; Dan-Hui Yang; Shui-Zi Ding; Cheng Lei; Rong-Chun Wang; Lv Liu; Xi Kang; Xiao-Qing Shen; Yi-Feng Yang; Zhi-Ping Tan; Yue-Qiu Tan; et al. (Human Genetics, 2021)

Improving Oral Bioavailability of Luteolin Nanocrystals by Surface Modification of Sodium Dodecyl Sulfate - Jiali Liu; Yongbing Sun; Meng Cheng; Qiaoming Liu; Wan Liu; Chao Gao; Jianfang Feng; Yi Jin; Liangxing Tu (AAPS PharmSciTech, 2021)

Interest-activity symptom severity predicts response to ketamine infusion in treatment-resistant depression - Mu-Hong Chen; Wei-Chen Lin; Hui-Ju Wu; Ya-Mei Bai; Cheng-Ta Li; Shih-Jen Tsai; Chen-Jee Hong; Pei-Chi Tu; Tung-Ping Su (Psychopharmacology, 2021)

The Energy Principle of Coal and Gas Outbursts: Experimentally Evaluating the Role of Gas Desorption - Yang Lei; Yuanping Cheng; Ting Ren; Qingyi Tu; Longyong Shu; Yixuan Li (Rock Mechanics and Rock Engineering, 2021)

LncRNA ADAMTS9-AS1, as prognostic marker, promotes cell proliferation and EMT in colorectal cancer - Wanjing Chen; Qian Tu; Liang Yu; Yanyan Xu; Gang Yu; Benli Jia; Yunsheng Cheng; Yong Wang (Human Cell, 2020)

Three new species of Terriera (Rhytismatales, Ascomycota) from China - Shu-Rui Cai; Shi-Juan Wang; Tu Lv; Cheng-Lin Hou (Mycological Progress, 2020)

(±) Gancochlearols A and B: cytotoxic and COX-2 inhibitory meroterpenoids from Ganoderma cochlear - Fu-Ying Qin; Yong-Ming Yan; Zheng-Chao Tu; Yong-Xian Cheng (Natural Product Research, 2020)

Distribution patterns and source identification for heavy metals in Mirs Bay of Hong Kong in China - Mei-Lin Wu; Hao Cheng; Hui Zhao; Fu-Lin Sun; Yu-Tu Wang; Jian-Ping Yin; Jiao Fei; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Phytoplankton community, structure and succession delineated by partial least square regression in Daya Bay, South China Sea - Mei-Lin Wu; Yu-Tu Wang; Hao Cheng; Fu-lin Sun; Jiao Fei; Cui-Ci Sun; Jian-Ping Yin; Hui Zhao; You-Shao Wang (Ecotoxicology, 2020)

Driving forces of China’s multisector CO2 emissions: a Log-Mean Divisia Index decomposition - Wei Pan; Haiting Tu; Cheng Hu; Wulin Pan (Environmental Science and Pollution Research, 2020)

Flood-resilient urban design based on the indigenous landscape in the city of Can Tho, Vietnam - Nguyen Van Long; Yuning Cheng; Tu Dam Ngoc Le (Urban Ecosystems, 2020)

Geological Control of Fold Structure on Gas Occurrence and Its Implication for Coalbed Gas Outburst: Case Study in the Qinan Coal Mine, Huaibei Coalfield, China - Kaizhong Zhang; Liang Wang; Yuanping Cheng; Wei Li; Jin Kan; Qingyi Tu; Jingyu Jiang (Natural Resources Research, 2020)

Selenate Reduction and Selenium Enrichment of Tea by the Endophytic Herbaspirillum sp. Strain WT00C - Xiao Xu; Wei Cheng; Xin Liu; Heng You; Guitai Wu; Kunming Ding; Xiuliang Tu; Lanfang Yang; Youpin Wang; Yadong Li; Haoshuang Gu; Xingguo Wang (Current Microbiology, 2020)

Fabrication of Fine Puerarin Nanocrystals by Box–Behnken Design to Enhance Intestinal Absorption - Meng Cheng; Fangying Yuan; Jiali Liu; Wan Liu; Jianfang Feng; Yi Jin; Liangxing Tu (AAPS PharmSciTech, 2020)

SlCAND1, encoding cullin-associated Nedd8-dissociated protein 1, regulates plant height, flowering time, seed germination, and root architecture in tomato - Wenjing Cheng; Shuangqin Yin; Yun Tu; Hu Mei; Yongzhong Wang; Yingwu Yang (Plant Molecular Biology, 2020)

Speciation and sorption structure of diphenylarsinic acid in soil clay mineral fractions using sequential extraction and EXAFS spectroscopy - Meng Zhu; Xuefeng Hu; Chen Tu; Yongming Luo; Ruyi Yang; Shoubiao Zhou; Nannan Cheng; Elizabeth L. Rylott (Journal of Soils and Sediments, 2020)

Comparative Study of Regulations of Devices for Aesthetic Purposes: US, European Union, China, and Taiwan - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2020)

Novel mutations in SPEF2 causing different defects between flagella and cilia bridge: the phenotypic link between MMAF and PCD - Chaofeng Tu; Hongchuan Nie; Lanlan Meng; Weili Wang; Haiyu Li; Shimin Yuan; Dehua Cheng; Wenbin He; Gang Liu; Juan Du; Fei Gong; Guangxiu Lu; et al. (Human Genetics, 2020)

An Approach for Diver Passive Detection Based on the Established Model of Breathing Sound Emission - Qiang Tu; Fei Yuan; Weidi Yang; En Cheng (Journal of Marine Science and Engineering, 2020)
Diver breathing sounds can be used as a characteristic for the passive detection of divers. This work introduces an approach for detecting the presence of a diver based on diver breathing sounds signals. An underwater channel model for passive diver detection is built to evaluate the impacts of acoustic energy transmission loss and ambient noise interference. The noise components of the observed signals are suppressed by spectral subtraction based on block-based threshold theory and smooth minimal statistic noise tracking theory. Then the envelope spectrum features of the denoised signal are extracted for diver detection. The performance of the proposed detection method is demonstrated through experimental analysis and numerical modeling.

Atmospheric mercury accumulation rate in northeastern China during the past 800 years as recorded by the sediments of Tianchi Crater Lake - Tao Zhan; Xin Zhou; Wenhan Cheng; Xiaoqing He; Luyao Tu; Xiaoyan Liu; Junyi Ge; Yuanyun Xie; Jun Zhang; Yongfa Ma; E Li; Yansong Qiao (Environmental Science and Pollution Research, 2020)

Role of Tectonic Coal in Coal and Gas Outburst Behavior During Coal Mining - Qingyi Tu; Yuanping Cheng; Ting Ren; Zhenyang Wang; Jia Lin; Yang Lei (Rock Mechanics and Rock Engineering, 2019)

Three new Coccomyces species from Shennongjia National Nature Reserve in China - Tu Lv; Wan-Peng Tang; Shu-Rui Cai; Cheng-Lin Hou (Mycological Progress, 2019)

Food-derived antithrombotic peptides: Preparation, identification, and interactions with thrombin - Shuzheng Cheng; Maolin Tu; Hanxiong Liu; Guanghua Zhao; Ming Du (Critical Reviews in Food Science and Nutrition, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Interfacial Stress in the Development of Biologics: Fundamental Understanding, Current Practice, and Future Perspective - Jinjiang Li; Mary E. Krause; Xiaodong Chen; Yuan Cheng; Weiguo Dai; John J. Hill; Min Huang; Susan Jordan; Daniel LaCasse; Linda Narhi; Evgenyi Shalaev; Ian C. Shieh; et al. (The AAPS Journal, 2019)

Variance in heavy metal leachability of Pb-, Ni-, and Cr-contaminated soils through red brick sintering procedure - Shyh-Wei Chen; Pei-Cheng Cheng; Yao-Ting Tu; Chang-Chao Chen; Shu-Fen Cheng (Environmental Monitoring and Assessment, 2019)

Correction to: Magnesium deficiency affects secondary lignification of the vascular system in Citrus sinensis seedlings - Jing-Hao Huang; Jing Xu; Xin Ye; Tu-Yan Luo; Li-Hua Ren; Guo-Cheng Fan; Yi-Ping Qi; Qiang Li; Rhuanito S. Ferrarezi; Li-Song Chen (Trees, 2019)

Magnesium deficiency affects secondary lignification of the vascular system in Citrus sinensis seedlings - Jing-Hao Huang; Jing Xu; Xin Ye; Tu-Yan Luo; Li-Hua Ren; Guo-Cheng Fan; Yi-Ping Qi; Qiang Li; Rhuanito S. Ferrarezi; Li-Song Chen (Trees, 2019)

AtDIV2, an R-R-type MYB transcription factor of Arabidopsis, negatively regulates salt stress by modulating ABA signaling - Qing Fang; Qiong Wang; Hui Mao; Jing Xu; Ying Wang; Hao Hu; Shuai He; Junchu Tu; Chao Cheng; Guozheng Tian; Xianqiang Wang; Xiaopeng Liu; et al. (Plant Cell Reports, 2018)

Web-Based Experience Sharing Platform on Medical Device Incidents for Clinical Engineers in Hospitals - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Yu-Wen Huang; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2018)

Biomechanical Study on the Cyclic Stability of Distal Radius C2 Type Osteoporotic Fractures Using Locking Plates in a Cadaver Model - Chih-Kun Hsiao; Yuan-Kun Tu; Cheng-Hung Lee; Cheng-Yo Yen; Feng-Chen Kao; Yi-Jung Tsai (Journal of Medical and Biological Engineering, 2018)

Postnatal Subacute Benzo(a)Pyrene Exposure Caused Neurobehavioral Impairment and Metabolomic Changes of Cerebellum in the Early Adulthood Period of Sprague-Dawley Rats - Chunlin Li; Jing Wang; Qiuping Su; Kai Yang; Chengzhi Chen; XueJun Jiang; Tingli Han; Shuqun Cheng; Tingting Mo; Ruiyuan Zhang; Bin Peng; Yuming Guo; et al. (Neurotoxicity Research, 2018)

Modeling Pollutant Buildup and Washoff Parameters for SWMM Based on Land Use in a Semiarid Urban Watershed - Min-Cheng Tu; Patricia Smith (Water, Air, & Soil Pollution, 2018)

Combination of High-Sensitivity C-Reactive Protein and Homocysteine Predicts the Post-Stroke Depression in Patients with Ischemic Stroke - Li-Shan Cheng; Wen-Jun Tu; Yuan Shen; Li-Jun Zhang; Kangxiang Ji (Molecular Neurobiology, 2018)

Schwann-Cell Autophagy, Functional Recovery, and Scar Reduction After Peripheral Nerve Repair - Po-Yen Ko; Cheng-Chang Yang; Yao-Lung Kuo; Fong-Chin Su; Tai-I Hsu; Yuan-Kun Tu; I-Ming Jou (Journal of Molecular Neuroscience, 2018)

Genome-wide identification and expression profile analysis of the HOG gene family in Aspergillus oryzae - Bin He; Yayi Tu; Zhihong Hu; Long Ma; Jing Dai; Xiaojie Cheng; Haoran Li; Lanlan Liu; Bin Zeng (World Journal of Microbiology and Biotechnology, 2018)

Evaluation of the parameters affecting bone temperature during drilling using a three-dimensional dynamic elastoplastic finite element model - Yung-Chuan Chen; Yuan-Kun Tu; Jun-Yan Zhuang; Yi-Jung Tsai; Cheng-Yo Yen; Chih-Kun Hsiao (Medical & Biological Engineering & Computing, 2017)

Protodioscin ameliorates oxidative stress, inflammation and histology outcome in Complete Freund’s adjuvant induced arthritis rats - Jia-Yu Liu; Ya-Ling Hou; Rong Cao; Hong Xia Qiu; Guo-Hua Cheng; Ran Tu; Li Wang; Jun-Li Zhang; Dan Liu (Apoptosis, 2017)

Genetic analysis of porcine circovirus type 2 in China - Cheng-Gang Jiang; Gang Wang; Ya-Bin Tu; Yong-Gang Liu; Shu-Jie Wang; Xue-Hui Cai; Tong-Qing An (Archives of Virology, 2017)

Climatic and geographic factors affect ecosystem multifunctionality through biodiversity in the Tibetan alpine grasslands - Ying Pan; Jun-xi Wu; Li-ming Luo; Yan-li Tu; Cheng-qun Yu; Xian-zhou Zhang; Yan-jun Miao; Yan Zhao; Jun-ling Yang (Journal of Mountain Science, 2017)

Resveratrol protects the loss of connexin 43 induced by ethanol exposure in neonatal mouse cardiomyocytes - Su Tu; Fu-tao Cao; Xiao-chun Fan; Cheng-jian Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2017)

Influenza A virus upregulates PRPF8 gene expression to increase virus production - Chee-Hing Yang; Hui-Chun Li; Yu-Ling Shiu; Tzu-Shan Ku; Chia-Wen Wang; Yi-Shuan Tu; Hung-Ling Chen; Cheng-Hao Wu; Shih-Yen Lo (Archives of Virology, 2017)

MR image segmentation and bias field estimation based on coherent local intensity clustering with total variation regularization - Xiaoguang Tu; Jingjing Gao; Chongjing Zhu; Jie-Zhi Cheng; Zheng Ma; Xin Dai; Mei Xie (Medical & Biological Engineering & Computing, 2016)

Experimental Study of Coal and Gas Outbursts Related to Gas-Enriched Areas - Qingyi Tu; Yuanping Cheng; Pinkun Guo; Jingyu Jiang; Liang Wang; Rong Zhang (Rock Mechanics and Rock Engineering, 2016)

A galactopoiesis accordant yield of functional recombinant human factor IX from homozygous transgenic pigs requires a large amount of vitamin K supplementation - Chon-Ho Yen; Tien-Shuh Yang; Yin-Shen Lin; Meng-Hwan Lee; Kuo-Cheng Yu; Chung-Lin Huang; How-Hong Hsieh; Ching-Fu Tu (Transgenic Research, 2016)

Folic Acid Attenuates Vascular Endothelial Cell Injury Caused by Hypoxia via the Inhibition of ERK1/2/NOX4/ROS Pathway - Fei Cheng; Jun Lan; Wenhao Xia; Chang Tu; Benfa Chen; Shicheng Li; Weibiao Pan (Cell Biochemistry and Biophysics, 2016)

Interleukin-12 inhibits the hepatocellular carcinoma growth by inducing macrophage polarization to the M1-like phenotype through downregulation of Stat-3 - Qin Wang; Feng Cheng; Ting-ting Ma; Hai-Yu Xiong; Zi-Wei Li; Chang-Li Xie; Cui-Ying Liu; Zhi-Guang Tu (Molecular and Cellular Biochemistry, 2016)

Humic acids enhance the microbially mediated release of sedimentary ferrous iron - Chun-Han Chang; Chia-Cheng Wei; Li-Hung Lin; Tzu-Hsuan Tu; Vivian Hsiu-Chuan Liao (Environmental Science and Pollution Research, 2016)

Identification of rare variants in TNNI3 with atrial fibrillation in a Chinese GeneID population - Chuchu Wang; Manman Wu; Jin Qian; Bin Li; Xin Tu; Chengqi Xu; Sisi Li; Shanshan Chen; Yuanyuan Zhao; Yufeng Huang; Lisong Shi; Xiang Cheng; et al. (Molecular Genetics and Genomics, 2016)

Genomic analysis of Staphylococcus phage Stau2 isolated from medical specimen - Sue-Er Hsieh; Yi-Hsiung Tseng; Hsueh-Hsia Lo; Shui-Tu Chen; Cheng-Nan Wu (Virus Genes, 2016)

Validation of cross-contamination control in biological safety cabinet for biotech/pharmaceutical manufacturing process - Shih-Cheng Hu; Angus Shiue; Jin-Xin Tu; Han-Yang Liu; Rong-Ben Chiu (Environmental Science and Pollution Research, 2015)

IL-12 could induce monocytic tumor cells directional differentiation - Ting-ting Ma; Bi-Tao Wu; Yan Lin; Hai-Yu Xiong; Qin Wang; Zi-Wei Li; Feng Cheng; Zhi-Guang Tu (Molecular and Cellular Biochemistry, 2015)

Risk assessment of environmental corrosion for reinforcing steel bars embedded in concrete in Taiwan - Chien-Kuo Chiu; Fung-Chung Tu; Cheng-Yu Fan (Natural Hazards, 2015)

IL-17A promotes ventricular remodeling after myocardial infarction - Su-Feng Zhou; Jing Yuan; Meng-Yang Liao; Ni Xia; Ting-Ting Tang; Jing-Jing Li; Jiao Jiao; Wen-Yong Dong; Shao-Fang Nie; Zheng-Feng Zhu; Wen-Cai Zhang; Bing-Jie Lv; et al. (Journal of Molecular Medicine, 2014)

A bioinformatics method for predicting long noncoding RNAs associated with vascular disease - JianWei Li; Cheng Gao; YuChen Wang; Wei Ma; Jian Tu; JunPei Wang; ZhenZhen Chen; Wei Kong; QingHua Cui (Science China Life Sciences, 2014)

Design, synthesis, and biological study of 6,7-dihydro-5H-pyrano[2,3-d]pyrimidine derivatives as novel hedgehog signaling pathway inhibitors - Minhang Xin; Liandi Zhang; Han Shen; Jun Wen; Chongxing Tu; Zhaoyu Liu; Lingfei Cheng; Xinge Zhao (Medicinal Chemistry Research, 2014)

Impact of Effective Stress and Matrix Deformation on the Coal Fracture Permeability - Pinkun Guo; Yuanping Cheng; Kan Jin; Wei Li; Qingyi Tu; Hongyong Liu (Transport in Porous Media, 2014)

Early lethality of shRNA-transgenic pigs due to saturation of microRNA pathways - Zhen Dai; Rong Wu; Yi-cheng Zhao; Kan-kan Wang; Yong-ye Huang; Xin Yang; Zi-cong Xie; Chang-chun Tu; Hong-sheng Ouyang; Tie-dong Wang; Da-xin Pang (Journal of Zhejiang University-SCIENCE B, 2014)

Shear wave velocity measurements and soil–pile system identifications in dynamic centrifuge tests - Chung-Jung Lee; Wen-Yi Hung; Chen-Hui Tsai; Ting Chen; Yichun Tu; Chin-Cheng Huang (Bulletin of Earthquake Engineering, 2014)

Sirt1 Promotes Axonogenesis by Deacetylation of Akt and Inactivation of GSK3 - Xiao-hong Li; Chong Chen; Yue Tu; Hong-tao Sun; Ming-liang Zhao; Shi-xiang Cheng; Yang Qu; Sai Zhang (Molecular Neurobiology, 2013)

Deformable Templates Guided Discriminative Models for Robust 3D Brain MRI Segmentation - Cheng-Yi Liu; Juan Eugenio Iglesias; Zhuowen Tu (Neuroinformatics, 2013)

Identification and assessment of heavy rainfall–induced disaster potentials in Taipei City - Jui-Sheng Chou; Kuo-Hsin Yang; Min-Yuan Cheng; Wan-Ting Tu (Natural Hazards, 2013)

Effects of pyrene on antioxidant systems and lipid peroxidation level in mangrove plants, Bruguiera gymnorrhiza - Hui Song; You-Shao Wang; Cui-Ci Sun; Yu-Tu Wang; Ya-Lan Peng; Hao Cheng (Ecotoxicology, 2012)

Mapping of BnMs4 and BnRf to a common microsyntenic region of Arabidopsis thaliana chromosome 3 using intron polymorphism markers - Shengqian Xia; Ling Cheng; Feng Zu; Xiaoling Dun; Zhengfu Zhou; Bin Yi; Jing Wen; Chaozhi Ma; Jinxiong Shen; Jinxing Tu; Tingdong Fu (Theoretical and Applied Genetics, 2012)

Acute effects of plyometric jumping and intermittent running on serum bone markers in young males - Che-Fu Lin; Tsang-hai Huang; Kuo-Cheng Tu; Linda L. Lin; Yi-Hsuan Tu; Rong-Sen Yang (European Journal of Applied Physiology, 2012)

Fast Approximate Stochastic Tractography - Juan Eugenio Iglesias; Paul M. Thompson; Cheng-Yi Liu; Zhuowen Tu (Neuroinformatics, 2012)

A new viewpoint on risk control decision models for natural disasters - Chun-Pin Tseng; Cheng-Wu Chen; Yu-Ping Tu (Natural Hazards, 2011)

Genetic analysis of fish iridoviruses isolated in Taiwan during 2001–2009 - Sue-Min Huang; Chen Tu; Chun-Hsien Tseng; Chin-Cheng Huang; Chi-Chung Chou; Hung-Chih Kuo; Shao-Kuang Chang (Archives of Virology, 2011)

Shiga toxin type 2 (Stx2), a potential agent of bioterrorism, has a short distribution and a long elimination half-life, and induces kidney and thymus lesions in rats - Yue-Nan Liu; Sheng-han Wang; Tao Li; Qin Wang; Wei Tu; Kun Cai; Xiao-Jun Hou; Ren-Mao Tian; Xiang Gao; Hao Liu; Le Xiao; Jing Shi; et al. (Archives of Toxicology, 2011)

Evaluation and improvement of a SVD-based empirical atmospheric model - Jia-Yuh Yu; Cheng-Wei Chang; Jien-Yi Tu (Advances in Atmospheric Sciences, 2011)

Polyclonal rabbit anti-murine plasmacytoma cell globulins induce myeloma cells apoptosis and inhibit tumour growth in mice - Bo Mu; Jin-liang Yang; Lan-tu Gou; Yu-qin Yao; Yan Zhou; Zhi-hui Cheng; Hua-shan Shi; Zhi-yong Li; Yuan Wen; Fei Leng; Feng-yu Cui; Tian-tai Ma; et al. (Apoptosis, 2011)

Significant association of SNP rs2106261 in the ZFHX3 gene with atrial fibrillation in a Chinese Han GeneID population - Cong Li; Fan Wang; Yanzong Yang; Fenfen Fu; Chengqi Xu; Lisong Shi; Sisi Li; Yunlong Xia; Gang Wu; Xiang Cheng; Hui Liu; Chuchu Wang; et al. (Human Genetics, 2011)

Trends in temperature extremes in association with weather-intraseasonal fluctuations in eastern China - Cheng Qian; Zhongwei Yan; Zhaohua Wu; Congbin Fu; Kai Tu (Advances in Atmospheric Sciences, 2011)

Rapid simultaneous screening of seven clinically important enteric pathogens using a magnetic bead based DNA microarray - Hong Sun; Qiu-Hua Mo; Ji-Can Lin; Ze Yang; Cheng-Ning Tu; Da-Yong Gu; Lei Shi; Wei-Ping Lu (World Journal of Microbiology and Biotechnology, 2011)

Regulation of subtilisin‐like protease prC expression by nematode cuticle in the nematophagous fungus Clonostachys rosea - Cheng‐Gang Zou; Nan Tao; Wen‐Jing Liu; Jin‐Kui Yang; Xiao‐Wei Huang; Xian‐Yong Liu; Hui‐Hui Tu; Zhong‐Wei Gan; Ke‐Qin Zhang (Environmental Microbiology, 2010)
Summary Nematophagous fungi have been used as biological control agents against nematodes parasitic to plants and animals. These fungi can secret subtilisin‐like extracellular serine proteases during the infection of nematodes. The expression of these subtilisin‐like serine proteases is regulated by nitrogen sources, including nematode cuticle. However, the mechanisms underlying the nitrogen sources‐induced expression of these serine proteases is not well understood. In this study, we investigated the effect of nitrogen sources on the expression of a subtilisin‐like extracellular protease, prC , in the nematophagous fungus Clonostachys rosea . Disruption of prC attenuated infection of the fungus to nematodes, indicating that this gene functions as a virulence factor. The inhibition of basal expression of prC by the preferred nitrogen sources (glutamine, ammonia) occurred at the transcriptional level. In contrast, nematode cuticle induced the expression of prC at the post‐transcriptional level. The inducible expression of prC by nematode cuticle was significantly suppressed by glutamine, ammonia and phenylmethylsulfonyl fluoride (an inhibitor of serine protease). Thus, the existence of active PrC, albeit at a low level in the medium, is probably essential for further induction of this gene by nematode cuticle. Moreover, the low molecule weight ( prC . Ammonia suppresses the virulence of C. rosea against nematodes, probably by inhibiting prC expression. Thus, the nematophagous fungi probably could not function well as biocontrol agents in fields fertilized with a large amount of ammonium salt.

Roles of cysteines Cys115 and Cys201 in the assembly and thermostability of grouper betanodavirus particles - Chun-Hsiung Wang; Chi-Hsin Hsu; Yi-Min Wu; Yu-Chun Luo; Mei-Hui Tu; Wei-hau Chang; R. Holland Cheng; Chan-Shing Lin (Virus Genes, 2010)

Role of mast cells, stem cell factor and protease-activated receptor-2 in tubulointerstitial lesions in IgA nephropathy - Hong Liu; Fuyou Liu; Youming Peng; Yinghong Liu; Lingyan Li; Xiwen Tu; Meichu Cheng; Xiangqing Xu; Xing Chen; Guanghui Ling; Lin Sun (Inflammation Research, 2010)

PacC in the nematophagous fungus Clonostachys rosea controls virulence to nematodes - Cheng‐Gang Zou; Hui‐Hui Tu; Xian‐Yong Liu; Nan Tao; Ke‐Qin Zhang (Environmental Microbiology, 2010)
Summary Nematophagous fungi are commonly used as biological control agents of plant and animal parasitic nematodes. However, relatively little is known of the environmental attributes conferring pathogenicity in these fungi. In this report, we investigated the role of PacC‐mediated pH response in the pathogenesis of the nematophagous fungus Clonostachys rosea . We identified a pacC orthologue from this fungus and found that its transcript was elevated in C. rosea during the early stage of its infection of nematode. Disruption of pacC resulted in slowed growth at alkaline pH, altered filamentation, reduced conidiation and attenuated virulence to nematodes. The expression of an extracellular serine protease PrC , a putative virulence factor, was downregulated in the pacC mutants. The PrC transcript levels were significantly higher under alkaline growth conditions than under acidic growth conditions. Promoter activity analysis and electrophoretic mobility shift assay indicated that the regulation of PrC by pH via the PacC pathway occurred at the transcriptional level. In conclusion, PacC functions as a positive regulator of virulence to nematodes in C. rosea .

Association Analysis of the RET Proto-Oncogene with Hirschsprung Disease in the Han Chinese Population of Southeastern China - Cui-Ping Liu; Qian-Qian Tang; Jin-Tu Lou; Chun-Fen Luo; Xue-Wu Zhou; Dong-Mei Li; Fei Chen; Xiang Li; Ji-Cheng Li (Biochemical Genetics, 2010)

Chloroplast transformation of rapeseed (Brassica napus) by particle bombardment of cotyledons - Lin Cheng; He-Ping Li; Bo Qu; Tao Huang; Jin-Xing Tu; Ting-Dong Fu; Yu-Cai Liao (Plant Cell Reports, 2010)

Medium optimization for the feather-degradation by Streptomyces fradiae Var S-221 using the response surface methodology - Xin Cheng; Lin Huang; Xiao-rong Tu; Kun-tai Li (Biodegradation, 2010)

The influence of plectin deficiency on stability of cytokeratin18 in hepatocellular carcinoma - Chiung-Chi Cheng; Yi-Hsiang Liu; Chin-Chin Ho; Wei-Ting Chao; Ren-Jeng Pei; Yung-Hsiang Hsu; Kun-Tu Yeh; Lu-Chang Ho; Ming-Chuang Tsai; Yih-Shyong Lai (Journal of Molecular Histology, 2008)

Parallel computation of seismic analysis of high arch dam - Houqun Chen; Huaifa Ma; Jin Tu; Guangqing Cheng; Juzhen Tang (Earthquake Engineering and Engineering Vibration, 2008)

Spatial Variability of Turbulent Fluxes in the Roughness Sublayer of an Even-Aged Pine Forest - Gabriel Katul; Cheng-I Hsieh; David Bowling; Kenneth Clark; Narasinha Shurpali; Andrew Turnipseed; John Albertson; Kevin Tu; Dave Hollinger; Bob Evans; Brian Offerle; Dean Anderson; et al. (Boundary-Layer Meteorology, 1999)

Specific protein phosphorylation induced in Xanthomonas campestris pv. oryzae by bacteriophage Xp12 - Ching-Ming Cheng; Jenn Tu; Chen-Chung Yang; Tsong-Teh Kuo (Archives of Microbiology, 1994)

Specific protein phosphorylation induced in Xanthomonas campestris pv. oryzae by bacteriophage Xp12 - Tsong-Teh Kuo; Ching-Ming Cheng; Jenn Tu; Chen-Chung Yang (Archives of Microbiology, 1994)